Hot-rolled steel sheet, hot-dip plated steel sheet, and method for producing hot-rolled steel sheet

By controlling the chemical composition and manufacturing process of hot-rolled steel plates, the technical problems of hot-rolled steel plates in terms of high strength, excellent processability, excellent LME resistance and high rigidity are solved, especially when hot-dip galvanized plating, effectively suppressing brittle cracks of molten metals, achieving an improvement in overall performance.

CN118251512BActive Publication Date: 2025-04-25NIPPON STEEL CORPORATION
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202280074678.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-11-12
Filing Date
2022-09-22
Publication Date
2025-04-25
Estimated Expiration
2042-09-22

AI Technical Summary

Technical Problem

The prior art fails to meet the needs of hot-rolled steel sheets for high strength, excellent processability, excellent LME resistance and high rigidity, especially when hot-dip galvanized coatings are formed on the surface, it is easy to cause molten metal brittle cracks.

Method used

By controlling the chemical composition and manufacturing process of the hot-rolled steel plate, it is ensured that the steel plate contains a specific range of elements, such as C, Si, Mn, P, S, Al, N, Ti, B, and achieve a specific bainite ferrite area ratio, dislocation density and Ti carbide average circular equivalent diameter in the microstructure. At the same time, a specific cooling process and coiling temperature are used to form a hot-dip plated steel plate with excellent performance.

Benefits of technology

The comprehensive performance of hot-rolled steel plates with high strength, excellent processability, excellent LME resistance and high rigidity is achieved, especially in the case of hot-dip galvanized plating, which effectively suppresses the occurrence of brittle cracks of molten metals.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004829653510000371
    Figure BDA0004829653510000371
  • Figure BDA0004829653510000391
    Figure BDA0004829653510000391
  • Figure BDA0004829653510000411
    Figure BDA0004829653510000411
Patent Text Reader

Abstract

Provided is a hot-rolled steel sheet having high strength, excellent workability, excellent LME resistance, and excellent rigidity. The hot-rolled steel sheet of the present embodiment contains, by mass%, C: 0.040-0.120%, Si: 0.01-0.60%, Mn: 0.50-1.50%, P: 0.025% or less, S: 0.010% or less, Al: 0.010-0.070%, N: 0.0070% or less, Ti: 0.055-0.200%, and B: 0.0010-0.0050%, with the remainder being Fe and impurities, and in the microstructure, the area ratio of bainitic ferrite is 85% or more, and the dislocation density is 8.0×10 13 / m 2 ~100.0×10 13 / m 2 The average circle-equivalent diameter of Ti carbides in the hot-rolled steel sheet is 10 nm or less, and the average circle-equivalent diameter of bainitic ferrite grains is 15 μm or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a hot-rolled steel sheet, a hot-dip galvanized steel sheet having a hot-dip galvanized layer formed on the surface of the hot-rolled steel sheet, and a method for producing the hot-rolled steel sheet. Background Art

[0002] Hot rolled steel sheets are widely used in automobiles, motors, building materials, and construction machinery. Hot rolled steel sheets used for these purposes require high strength. On the other hand, hot rolled steel sheets are processed into various shapes for the above purposes. Therefore, hot rolled steel sheets are required to have not only high strength but also excellent processability.

[0003] Technologies for improving the strength and workability of hot-rolled steel sheets are proposed in Japanese Patent Application Publication No. 2018-003062 (Patent Document 1) and Japanese Patent Application Publication No. 2017-179539 (Patent Document 2).

[0004] The hot rolled steel sheet disclosed in Patent Document 1 has the following chemical composition: by mass %, C: 0.04-0.18%, Si: 0.2-2.0%, Mn: 1.0-3.0%, P: 0.03% or less, S: 0.005% or less, Al: 0.01-0.100%, N: 0.010% or less, Ti: 0.03-0.15%, Cr: 0.10-0.50%, B: 0.0005-0.0050%, and the balance is Fe and inevitable impurities. In the microstructure of the hot rolled steel sheet, the area ratio of the bainite phase is 85% or more, the area ratio of the austenite phase is 1-8%, and the area ratio of the martensite phase is 3% or less. Moreover, the grains of the austenite phase with a diameter of 0.8 μm or less account for more than 70% of the entire austenite phase.

[0005] Patent Document 1 discloses that the microstructure of a hot-rolled steel sheet mainly includes a bainite phase and fine austenite phases are dispersed in the bainite phase, thereby providing high strength and excellent workability.

[0006] The hot rolled steel sheet disclosed in Patent Document 2 has the following chemical composition: in terms of mass %, C: 0.03-0.08%, Si: 0.01-1.50%, Mn: 0.1-1.5%, Ti: 0.05-0.15%, B: 0.0002-0.0030%, P: 0.1% or less, S: 0.005% or less, Al: 0.5% or less, N: 0.009% or less, the sum of Nb, Mo and V: 0-0.02%, and the sum of Ca and REM: 0-0.01%, with the remainder being Fe and impurities. Moreover, the mass ratio of the Ti content to the C content in the chemical composition (Ti / C) is 0.625-3.000. Moreover, in the hot rolled steel sheet, the dislocation density is 1×1014 m -2 ~1×10 16 m -2 Moreover, the average diameter of TiC precipitates in the grains is less than 2.0 nm, and the average number density of TiC precipitates in the grains is 1×10 17 Pieces / cm 3 ~5×10 18 Pieces / cm 3 Furthermore, the content of Ti in the crystal grains that is not on dislocations and exists in the form of TiC precipitates precipitated in the parent phase is 30 mass % or more of the total Ti content of the steel sheet.

[0007] In the hot-rolled steel sheet of Patent Document 2, a high tensile strength of 780 MPa or more can be obtained by increasing the dislocation density and forming TiC precipitates in the parent phase rather than on the dislocations. In addition, Patent Document 2 states that the workability of the hot-rolled steel sheet can be improved by suppressing the content of alloying elements.

[0008] In order to improve the corrosion resistance of the hot-rolled steel sheet, a hot-dip galvanized layer is sometimes formed on the surface of the hot-rolled steel sheet. Hereinafter, the hot-rolled steel sheet on which the hot-dip galvanized layer is formed is also referred to as a hot-dip plated steel sheet.

[0009] There are cases where a hot-rolled steel sheet (hot-dip galvanized steel sheet) with a hot-dip galvanized coating is welded to other steel members. During welding, a portion of the hot-dip galvanized coating melts. In addition, there are cases where the molten metal (zinc) enters the grain boundaries of the hot-rolled steel sheet and cracks are generated. Such cracks are called molten metal embrittlement cracks (LME: Liquid Metal Embrittlement).

[0010] Hot-rolled steel sheets are required to have not only high strength and excellent workability but also the property of suppressing the generation of LME when a hot-dip galvanizing layer is formed on the surface of the hot-rolled steel sheets (hereinafter, this property is also referred to as LME resistance).

[0011] Japanese Patent Application Publication No. 2018-145500 (Patent Document 3) proposes a hot-dip Zn-Al-Mg-based steel sheet having high strength, excellent workability, and excellent LME resistance.

[0012] The hot-dip Zn-Al-Mg-based steel sheet of Patent Document 3 comprises a base steel sheet and a hot-dip Zn-Al-Mg-based alloy layer. The base steel sheet has the following chemical composition: in terms of mass %, it contains C: 0.01-0.08%, Si: 0.8% or less, Mn: 0.5-1.8%, P: 0.05% or less, S: 0.005% or less, N: 0.001-0.005%, Ti: 0.02-0.2%, B: 0.0005-0.010%, Al: 0.005-0.1%, and the balance is Fe and unavoidable impurities. In the above chemical composition, the Ti / C equivalent ratio (=(Ti / 48) / (C / 12)) is 0.4-1.5. Moreover, in the base steel sheet, the dislocation density is 1.8×10 14 / m 2 ~5.7×10 14 / m 2 In the original steel plate, a single phase of either a bainitic ferrite phase or a ferrite phase, or a phase containing the bainitic ferrite phase and the ferrite phase is the main phase, and the area ratio of the hard second phase and cementite is 3% or less. In the original steel plate, carbides containing Ti with an average particle size of 20 nm or less are also dispersed.

[0013] In the hot-dip Zn—Al—Mg-based plated steel sheet of Patent Document 3, it is described that high strength, excellent workability, and excellent LME resistance can be obtained by having the above-mentioned chemical composition and microstructure.

[0014] Prior art literature

[0015] Patent Literature

[0016] Patent Document 1: Japanese Patent Application Publication No. 2018-003062

[0017] Patent Document 2: Japanese Patent Application Publication No. 2017-179539

[0018] Patent Document 3: Japanese Patent Application Publication No. 2018-145500 Summary of the invention

[0019] Problem that the invention aims to solve

[0020] However, in hot-rolled steel sheets, there are cases where not only high strength, excellent workability, and excellent LME resistance when a hot-dip galvanizing layer is formed, but also high rigidity is required. In the above-mentioned Patent Documents 1 to 3, although high strength, excellent workability, and excellent LME resistance when a hot-dip galvanizing layer is formed are studied, no research is conducted on a technology that can also obtain these characteristics and high rigidity.

[0021] An object of the present disclosure is to provide a hot-rolled steel sheet, a hot-dip plated steel sheet, and a method for producing a hot-rolled steel sheet having high strength, excellent workability, and excellent LME resistance as well as excellent rigidity.

[0022] Solutions for solving problems

[0023] The hot-rolled steel sheet, the hot-dip plated steel sheet, and the method for producing the hot-rolled steel sheet disclosed in the present invention have the following configurations.

[0024] The hot-rolled steel sheet disclosed herein contains, in terms of mass %,

[0025] C: 0.040~0.120%,

[0026] Si: 0.01-0.60%,

[0027] Mn: 0.50-1.50%,

[0028] P: 0.025% or less,

[0029] S: 0.010% or less,

[0030] Al: 0.010~0.070%,

[0031] N: 0.0070% or less,

[0032] Ti: 0.055 to 0.200%, and

[0033] B: 0.0010~0.0050%,

[0034] The balance is Fe and impurities.

[0035] In the microstructure, the area ratio of bainitic ferrite is more than 85%.

[0036] The dislocation density is 8.0×10 13 / m 2 ~100.0×10 13 / m 2 ,

[0037] The average circle-equivalent diameter of Ti carbides in the hot-rolled steel sheet is 10 nm or less.

[0038] The average circle-equivalent diameter of the bainitic ferrite grains is 15 μm or less.

[0039] The hot-rolled steel sheet disclosed herein contains, in terms of mass %,

[0040] C: 0.040~0.120%,

[0041] Si: 0.01-0.60%,

[0042] Mn: 0.50-1.50%,

[0043] P: 0.025% or less,

[0044] S: 0.010% or less,

[0045] Al: 0.010~0.070%,

[0046] N: 0.0070% or less,

[0047] Ti: 0.055 to 0.200%, and

[0048] B: 0.0010~0.0050%,

[0049] further comprising one or more selected from the group consisting of Group 1 and Group 2,

[0050] The balance is Fe and impurities.

[0051] In the microstructure, the area ratio of bainitic ferrite is more than 85%.

[0052] The dislocation density is 8.0×10 13 / m 2 ~100.0×10 13 / m 2 ,

[0053] The average circle-equivalent diameter of Ti carbides in the hot-rolled steel sheet is 10 nm or less.

[0054] The average circle equivalent diameter of the bainitic ferrite grains is 15 μm or less,

[0055] [Group 1]

[0056] One or more selected from the group consisting of Nb: 0.20% or less and V: 0.20% or less

[0057] [Group 2]

[0058] One or more selected from the group consisting of Cr: 1.0% or less and Mo: 1.0% or less.

[0059] The hot-dip plated steel sheet disclosed herein comprises:

[0060] The hot rolled steel sheet mentioned above; and

[0061] The hot-dip galvannealed coating layer is formed on the surface of the hot-rolled steel sheet and contains 65.00% or more of Zn in terms of mass%.

[0062] The method for producing a hot-rolled steel sheet disclosed herein comprises:

[0063] A rough rolling process uses a rough rolling mill to perform rough rolling on the billet to produce a rough bar;

[0064] a finishing rolling step of performing finish rolling on the rough bar material using a finishing rolling mill to produce a steel plate, wherein the finishing rolling temperature FT is set to 850° C. to 950° C.;

[0065] A cooling process, cooling the steel plate after finish rolling; and

[0066] a coiling step of coiling the steel sheet after the cooling step at a coiling temperature of 470° C. to 620° C.,

[0067] In the cooling process,

[0068] within 3 seconds after the finish rolling is completed, the cooling of the steel plate using a cooling device is started,

[0069] When the period from the start of cooling by the cooling device until the temperature of the steel sheet reaches the switching temperature ST is defined as the front cooling period, and the period from the switching temperature ST until the temperature of the steel sheet reaches the coiling temperature is defined as the back cooling period,

[0070] The front stage cooling rate CR1, which is the cooling rate in the front stage cooling period, is set to less than 25°C / sec.

[0071] The switching temperature ST is set to 730°C to 830°C,

[0072] The latter cooling rate CR2, which is the cooling rate in the latter cooling period, is set to 25° C. / sec or more.

[0073] Effects of the Invention

[0074] The hot-rolled steel sheet and hot-dip plated steel sheet disclosed in the present invention have high strength, excellent workability, excellent LME resistance, and excellent rigidity. The method for producing a hot-rolled steel sheet disclosed in the present invention can produce the hot-rolled steel sheet described above. BRIEF DESCRIPTION OF THE DRAWINGS

[0075] Figure 1 It is a schematic diagram of the LME resistance evaluation test in the examples.

[0076] Figure 2 Observed from the side Figure 1 Cross-sectional view of the LME resistance evaluation test. DETAILED DESCRIPTION

[0077] First, the present inventors studied hot-rolled steel sheets having high strength, excellent workability, and excellent LME resistance from the viewpoint of chemical composition. As a result, the present inventors have found that if the chemical composition of a hot-rolled steel sheet is set to the following chemical composition, there is a possibility that higher strength, excellent workability, and excellent LME resistance can be obtained, wherein the hot-rolled steel sheet contains, by mass%, C: 0.040-0.120%, Si: 0.01-0.60%, Mn: 0.50-1.50%, P: 0.025% or less, S: 0.010% or less, Al: 0.010-0.070%, N: 0.0070% or less, Ti: 0.055-0.200%, B: 0.0010-0.0050%, Nb: 0-0.20%, V: 0-0.20%, Cr: 0-1.0%, Mo: 0-1.0%, and the balance is Fe and impurities.

[0078] Therefore, in order to obtain higher strength, excellent workability, and excellent LME resistance, the microstructure of the hot-rolled steel sheet whose content of each element in the chemical composition is within the above range was further studied. As a result, the following knowledge was found: in the microstructure of the hot-rolled steel sheet, if the following technical characteristics are satisfied, higher strength, excellent workability, and excellent LME resistance can be obtained.

[0079] Technical feature 1: The area ratio of bainitic ferrite in the microstructure is 85% or more.

[0080] Technical feature 2: Dislocation density is 8.0×10 13 / m 2 ~100.0×10 13 / m 2 .

[0081] Technical feature 3: The average circle equivalent diameter of Ti carbides in the hot-rolled steel sheet is 10 nm or less.

[0082] However, even if the content of each element in the chemical composition is within the above range and satisfies technical features 1 to 3, the hot-rolled steel sheet still has low rigidity. Therefore, the inventors of the present invention have also studied means for obtaining higher rigidity by having higher strength, excellent workability, and excellent LME resistance. As a result, the following new insight was obtained: the hot-rolled steel sheet having the content of each element in the chemical composition within the above range and having technical features 1 to 3 also has the following technical feature 4, thereby having higher strength, excellent workability, and excellent LME resistance, and can also obtain higher rigidity.

[0083] Technical feature 4: The average circle equivalent diameter of bainitic ferrite grains is less than 15 μm.

[0084] The hot-rolled steel sheet, the hot-dip plated steel sheet using the hot-rolled steel sheet, and the method for producing the hot-rolled steel sheet according to the present embodiment are completed based on the above-mentioned technical ideas and have the following configurations.

[0085] [1] A hot-rolled steel sheet comprising, by mass%,

[0086] C: 0.040~0.120%,

[0087] Si: 0.01-0.60%,

[0088] Mn: 0.50-1.50%,

[0089] P: 0.025% or less,

[0090] S: 0.010% or less,

[0091] Al: 0.010~0.070%,

[0092] N: 0.0070% or less,

[0093] Ti: 0.055 to 0.200%, and

[0094] B: 0.0010~0.0050%,

[0095] The balance is Fe and impurities.

[0096] In the microstructure, the area ratio of bainitic ferrite is more than 85%.

[0097] The dislocation density is 8.0×10 13 / m 2 ~100.0×10 13 / m 2 ,

[0098] The average circle-equivalent diameter of Ti carbides in the hot-rolled steel sheet is 10 nm or less.

[0099] The average circle-equivalent diameter of the bainitic ferrite grains is 15 μm or less.

[0100] [2] A hot-rolled steel sheet containing, by mass%,

[0101] C: 0.040~0.120%,

[0102] Si: 0.01-0.60%,

[0103] Mn: 0.50-1.50%,

[0104] P: 0.025% or less,

[0105] S: 0.010% or less,

[0106] Al: 0.010~0.070%,

[0107] N: 0.0070% or less,

[0108] Ti: 0.055 to 0.200%, and

[0109] B: 0.0010~0.0050%,

[0110] further comprising one or more selected from the group consisting of Group 1 and Group 2,

[0111] The balance is Fe and impurities.

[0112] In the microstructure, the area ratio of bainitic ferrite is more than 85%.

[0113] The dislocation density is 8.0×10 13 / m 2 ~100.0×10 13 / m 2 ,

[0114] The average circle-equivalent diameter of Ti carbides in the hot-rolled steel sheet is 10 nm or less.

[0115] The average circle equivalent diameter of the bainitic ferrite grains is 15 μm or less,

[0116] [Group 1]

[0117] One or more selected from the group consisting of Nb: 0.20% or less and V: 0.20% or less,

[0118] [Group 2]

[0119] One or more selected from the group consisting of Cr: 1.0% or less and Mo: 1.0% or less.

[0120] [3] The hot-rolled steel sheet according to [2], wherein

[0121] The hot-rolled steel sheet includes the first group.

[0122] [4] The hot-rolled steel sheet according to [2] or [3], wherein

[0123] The hot-rolled steel sheet includes the second group.

[0124] [5] A hot-dip plated steel sheet comprising:

[0125] The hot-rolled steel sheet according to any one of [1] to [4]; and

[0126] The hot-dip galvannealed coating layer is formed on the surface of the hot-rolled steel sheet and contains 65.00% or more of Zn in terms of mass%.

[0127] [6] A method for producing a hot-rolled steel sheet, which is the method for producing a hot-rolled steel sheet according to any one of [1] to [4], comprising:

[0128] A rough rolling process uses a rough rolling mill to perform rough rolling on the billet to produce a rough bar;

[0129] a finishing rolling step of performing finish rolling on the rough bar material using a finishing rolling mill to produce a steel plate, wherein the finishing rolling temperature FT is set to 850° C. to 950° C.;

[0130] A cooling process, cooling the steel plate after finish rolling; and

[0131] a coiling step of coiling the steel sheet after the cooling step at a coiling temperature of 470° C. to 620° C.,

[0132] In the cooling process,

[0133] within 3 seconds after the finish rolling is completed, the cooling of the steel plate using a cooling device is started,

[0134] When the period from the start of cooling by the cooling device until the temperature of the steel sheet reaches the switching temperature ST is defined as the front cooling period, and the period from the switching temperature ST until the temperature of the steel sheet reaches the coiling temperature is defined as the back cooling period,

[0135] The front stage cooling rate CR1, which is the cooling rate in the front stage cooling period, is set to less than 25°C / sec.

[0136] The switching temperature ST is set to 730°C to 830°C,

[0137] The latter cooling rate CR2, which is the cooling rate in the latter cooling period, is set to 25° C. / sec or more.

[0138] Hereinafter, the hot-rolled steel sheet and the hot-dip plated steel sheet according to the present embodiment will be described in detail.

[0139] Unless otherwise stated, "%" concerning an element means mass %.

[0140] [Hot-rolled steel sheet]

[0141] [Chemical composition]

[0142] The chemical composition of the hot-rolled steel sheet according to the present embodiment contains the following elements.

[0143] C: 0.040~0.120%

[0144] Carbon (C) combines with Ti to form Ti carbide. Ti carbide increases the strength of the hot-rolled steel sheet due to precipitation strengthening, and also improves the workability. When the Ti content in the chemical composition is 0.055-0.200%, C is also prone to form bainitic ferrite. If the C content is less than 0.040%, even if the content of other elements is within the range of the present embodiment, higher strength cannot be obtained. Specifically, the tensile strength TS of the hot-rolled steel sheet is difficult to become more than 780 MPa. Moreover, the dislocation density becomes excessively high, and the workability of the hot-rolled steel sheet is reduced.

[0145] On the other hand, if the C content exceeds 0.120%, polygonal ferrite is easily generated in the microstructure even if the contents of other elements are within the range of the present embodiment. Therefore, the area ratio of bainitic ferrite of the hot-rolled steel sheet is reduced. Moreover, the dislocation density of the hot-rolled steel sheet is reduced. Moreover, the average circle equivalent diameter of the grains of bainitic ferrite also becomes coarse. As a result, the rigidity of the hot-rolled steel sheet is reduced.

[0146] Therefore, the C content is 0.040 to 0.120%.

[0147] The lower limit of the C content is preferably 0.042%, more preferably 0.044%, and further preferably 0.046%.

[0148] The upper limit of the C content is preferably 0.115%, more preferably 0.110%, and further preferably 0.105%.

[0149] Si: 0.01~0.60%

[0150] Silicon (Si) deoxidizes steel. Si also improves the strength of hot-rolled steel sheets by solid solution strengthening. If the Si content is less than 0.01%, the above effects cannot be fully obtained even if the contents of other elements are within the ranges of the present embodiment.

[0151] On the other hand, if the Si content exceeds 0.60%, polygonal ferrite is easily generated in the hot-rolled steel sheet even if the contents of other elements are within the range of the present embodiment. Therefore, the area ratio of bainitic ferrite of the hot-rolled steel sheet is reduced. Moreover, the dislocation density of the hot-rolled steel sheet is reduced. Moreover, the average equivalent circle diameter of the grains of bainitic ferrite also becomes coarse. As a result, the rigidity of the hot-rolled steel sheet is reduced.

[0152] Therefore, the Si content is 0.01 to 0.60%.

[0153] The lower limit of the Si content is preferably 0.02%, more preferably 0.03%, and further preferably 0.04%.

[0154] The upper limit of the Si content is preferably 0.55%, more preferably 0.50%, and further preferably 0.45%.

[0155] Mn: 0.50~1.50%

[0156] Manganese (Mn) improves the strength of the hot-rolled steel sheet by solid solution strengthening. If the Mn content is less than 0.50%, the above-mentioned effects cannot be fully obtained even if the contents of other elements are within the ranges of the present embodiment.

[0157] On the other hand, if the Mn content exceeds 1.50%, Mn segregation is likely to occur in the hot-rolled steel sheet even if the contents of other elements are within the range of the present embodiment. If the Mn content exceeds 1.50%, bainite is also likely to be generated in the hot-rolled steel sheet. Therefore, the area ratio of bainitic ferrite in the hot-rolled steel sheet decreases, and the dislocation density becomes excessively high. Therefore, the workability of the hot-rolled steel sheet is reduced.

[0158] Therefore, the Mn content is 0.50 to 1.50%.

[0159] The lower limit of the Mn content is preferably 0.55%, more preferably 0.60%, and further preferably 0.65%.

[0160] The upper limit of the Mn content is preferably 1.40%, more preferably 1.30%, and further preferably 1.20%.

[0161] P: 0.025% or less

[0162] Phosphorus (P) is an impurity. P segregates at grain boundaries and reduces the workability of hot-rolled steel sheets. P also reduces the weldability of hot-rolled steel sheets. If the P content exceeds 0.025%, the workability and weldability of the hot-rolled steel sheet are significantly reduced even if the contents of other elements are within the range of this embodiment.

[0163] Therefore, the P content is 0.025% or less.

[0164] The P content is preferably as low as possible. However, excessive reduction of the P content will reduce productivity and increase manufacturing costs. Therefore, considering the usual industrial production, the preferred lower limit of the P content is greater than 0%, more preferably 0.001%, more preferably 0.002%, and more preferably 0.003%.

[0165] The upper limit of the P content is preferably 0.023%, more preferably 0.020%, and further preferably 0.015%.

[0166] S: 0.010% or less

[0167] Sulfur (S) is an impurity. S segregates at grain boundaries and reduces the workability of the hot-rolled steel sheet. If the S content exceeds 0.010%, the workability of the hot-rolled steel sheet is significantly reduced even if the contents of other elements are within the ranges of the present embodiment.

[0168] Therefore, the S content is 0.010% or less.

[0169] The S content is preferably as low as possible. However, excessive reduction of the S content will reduce productivity and increase manufacturing costs. Therefore, considering the usual industrial production, the preferred lower limit of the S content is greater than 0%, more preferably 0.001%, more preferably 0.002%, and more preferably 0.003%.

[0170] The upper limit of the S content is preferably 0.009%, more preferably 0.008%.

[0171] Al: 0.010~0.070%

[0172] Aluminum (Al) deoxidizes steel. Al also combines with N to form Al nitride. This inhibits the combination of B and N. If the Al content is less than 0.010%, the above effects cannot be fully obtained even if the contents of other elements are within the ranges of the present embodiment.

[0173] On the other hand, if the Al content exceeds 0.070%, even if the contents of other elements are within the ranges of the present embodiment, coarse Al nitrides are excessively generated, thereby reducing the workability of the hot-rolled steel sheet.

[0174] Therefore, the Al content is 0.010 to 0.070%.

[0175] The lower limit of the Al content is preferably 0.012%, more preferably 0.014%, and further preferably 0.016%.

[0176] The upper limit of the Al content is preferably 0.065%, more preferably 0.060%, and further preferably 0.055%.

[0177] N: 0.0070% or less

[0178] Nitrogen (N) is an impurity. N combines with B to form BN, reducing the amount of dissolved B in the hot-rolled steel sheet. N also combines with Ti to form TiN, hindering the formation of Ti carbides. If the N content exceeds 0.0070%, BN and TiN will be excessively generated even if the contents of other elements are within the range of this embodiment. As a result, the LME resistance of the hot-rolled steel sheet is reduced. In addition, the strength of the hot-rolled steel sheet is also reduced.

[0179] Therefore, the N content is 0.0070% or less.

[0180] The N content is preferably as low as possible. However, excessive reduction of the N content will reduce productivity and increase manufacturing costs. Therefore, considering the usual industrial production, the preferred lower limit of the N content is greater than 0%, more preferably 0.0001%, more preferably 0.0005%, and more preferably 0.0010%.

[0181] The upper limit of the N content is preferably 0.0060%, more preferably 0.0050%, further preferably 0.0040%.

[0182] Ti: 0.055~0.200%

[0183] Titanium (Ti) combines with C to form Ti carbide. Ti carbide increases the strength of the hot-rolled steel sheet due to precipitation strengthening. Moreover, when the C content is 0.040-0.120%, if Ti is an appropriate content, bainitic ferrite is easily generated in the hot-rolled steel sheet. If the Ti content is less than 0.055%, polygonal ferrite is easily generated even if the content of other elements is within the range of the present embodiment. Therefore, the area ratio of bainitic ferrite of the hot-rolled steel sheet is reduced, and the dislocation density of the hot-rolled steel sheet is also reduced. Moreover, the average circle equivalent diameter of the grains of bainitic ferrite becomes coarse. As a result, the rigidity of the hot-rolled steel sheet is reduced.

[0184] On the other hand, if the Ti content exceeds 0.200%, even if the contents of other elements are within the ranges of the present embodiment, the dislocation density in the hot-rolled steel sheet becomes excessively high. As a result, the workability of the hot-rolled steel sheet decreases.

[0185] Therefore, the Ti content is 0.055 to 0.200%.

[0186] The lower limit of the Ti content is preferably 0.060%, more preferably 0.065%, further preferably 0.070%, further preferably 0.075%, further preferably 0.080%, further preferably 0.085%.

[0187] The upper limit of the Ti content is preferably 0.190%, more preferably 0.180%, further preferably 0.170%.

[0188] B: 0.0010~0.0050%

[0189] Boron (B) is solid-dissolved in the hot-rolled steel sheet and segregates at the old austenite grain boundaries. The segregated B increases the grain boundary strength. Therefore, B increases the LME resistance of the hot-rolled steel sheet. B also increases the hardenability of steel. If the B content is less than 0.0010%, even if the contents of other elements are within the range of the present embodiment, the LME resistance of the hot-rolled steel sheet cannot be fully obtained. Moreover, the hardenability is insufficient, so the dislocation density decreases. Moreover, the area ratio of bainitic ferrite decreases. Moreover, the starting temperature of the phase transformation from austenite to ferrite increases. In this case, the precipitation starting temperature of Ti carbide also increases. Therefore, Ti carbide becomes coarse. As a result, the strength of the hot-rolled steel sheet decreases and the rigidity also decreases.

[0190] On the other hand, if the B content exceeds 0.0050%, even if the contents of other elements are within the range of the present embodiment, the hardenability will be excessively increased. In this case, the dislocation density of the hot-rolled steel sheet becomes excessively high. Moreover, the area ratio of bainitic ferrite decreases. As a result, the workability of the steel sheet decreases. If the B content exceeds 0.0050%, the LME resistance is further reduced.

[0191] Therefore, the B content is 0.0010 to 0.0050%.

[0192] The lower limit of the B content is preferably 0.0015%, more preferably 0.0020%, and further preferably 0.0025%.

[0193] The upper limit of the B content is preferably 0.0045%, more preferably 0.0040%, and further preferably 0.0035%.

[0194] The balance of the chemical composition of the hot-rolled steel sheet of the present embodiment is Fe and impurities. Here, impurities refer to elements mixed from ore, waste materials, or manufacturing environment as raw materials during industrial production of hot-rolled steel sheets, and are not intentionally contained elements, but are allowed within a range that does not adversely affect the hot-rolled steel sheet of the present embodiment.

[0195] [optional elements]

[0196] The chemical composition of the hot-rolled steel sheet according to the present embodiment may further contain one or more selected from the group consisting of the first group and the second group in place of a part of Fe.

[0197] [Group 1]

[0198] One or more selected from the group consisting of Nb: 0.20% or less and V: 0.20% or less

[0199] [Group 2]

[0200] One or more selected from the group consisting of Cr: 1.0% or less and Mo: 1.0% or less

[0201] These are all arbitrary elements. The first group and the second group will be described below.

[0202] [Group 1: Nb and V]

[0203] The hot-rolled steel sheet of the present embodiment may contain the first group in place of a portion of Fe. These elements all form carbides by combining with C to improve the strength of the hot-rolled steel sheet. Each element will be described below.

[0204] Nb: 0.20% or less

[0205] Niobium (Nb) is an arbitrary element and may not be contained. In other words, the Nb content may be 0%.

[0206] When Nb is contained, that is, when the Nb content is greater than 0%, Nb combines with C to form Nb carbides. Nb carbides increase the strength of the hot-rolled steel sheet due to precipitation strengthening. The above effect can be obtained to a certain extent as long as a small amount of Nb is contained.

[0207] However, when the Nb content exceeds 0.20%, even if the contents of other elements are within the ranges of the present embodiment, Nb carbides are excessively generated. In this case, the workability of the hot-rolled steel sheet is reduced.

[0208] Therefore, the Nb content is 0 to 0.20%, and when contained, the Nb content is 0.20% or less.

[0209] The lower limit of the Nb content is preferably 0.01%, more preferably 0.05%, and further preferably 0.08%.

[0210] The upper limit of the Nb content is preferably 0.18%, more preferably 0.16%, and further preferably 0.14%.

[0211] V: 0.20% or less

[0212] Vanadium (V) is an arbitrary element, and V may not be contained. In other words, the V content may be 0%.

[0213] When V is contained, that is, when the V content is greater than 0%, V combines with C to form V carbides. V carbides increase the strength of the hot-rolled steel sheet due to precipitation strengthening. The above effect can be obtained to a certain extent as long as a small amount of V is contained.

[0214] However, if the V content exceeds 0.20%, even if the contents of other elements are within the ranges of the present embodiment, V carbides are excessively generated. In this case, the workability of the hot-rolled steel sheet is reduced.

[0215] Therefore, the V content is 0 to 0.20%, and when V is contained, the V content is 0.20% or less.

[0216] The lower limit of the V content is preferably 0.01%, more preferably 0.05%, and further preferably 0.08%.

[0217] The upper limit of the V content is preferably 0.18%, more preferably 0.16%, and further preferably 0.14%.

[0218] [Group 2: Cr and Mo]

[0219] The hot-rolled steel sheet of the present embodiment may contain the second group in place of a portion of Fe. These elements all improve the LME resistance of the hot-rolled steel sheet. Each element will be described below.

[0220] Cr: 1.0% or less

[0221] Chromium (Cr) is an arbitrary element, and Cr may not be contained. In other words, the Cr content may be 0%.

[0222] When Cr is contained, that is, when the Cr content is greater than 0%, Cr segregates at the prior austenite grain boundaries and improves the LME resistance of the hot-rolled steel sheet. The above effect can be obtained to a certain extent as long as a small amount of Cr is contained.

[0223] However, when the Cr content exceeds 1.0%, the workability of the hot-rolled steel sheet decreases even if the contents of other elements are within the ranges of the present embodiment.

[0224] Therefore, the Cr content is 0 to 1.0%, and when contained, the Cr content is 1.0% or less.

[0225] The lower limit of the Cr content is preferably 0.1%, more preferably 0.2%, and further preferably 0.3%.

[0226] The upper limit of the Cr content is preferably 0.9%, more preferably 0.8%, and further preferably 0.7%.

[0227] Mo: 1.0% or less

[0228] Molybdenum (Mo) is an arbitrary element and may not be contained. That is, the Mo content may be 0%. When contained, that is, when the Mo content is greater than 0%, Mo segregates at the old austenite grain boundary and improves the LME resistance of the hot-rolled steel sheet. As long as a small amount of Mo is contained, the above effect can be obtained to a certain extent.

[0229] However, if the Mo content exceeds 1.0%, the workability of the hot-rolled steel sheet decreases even if the contents of other elements are within the ranges of the present embodiment.

[0230] Therefore, the Mo content is 0 to 1.0%, and when contained, the Mo content is 1.0% or less.

[0231] The lower limit of the Mo content is preferably 0.1%, more preferably 0.2%, and further preferably 0.3%.

[0232] The upper limit of the Mo content is preferably 0.9%, more preferably 0.8%, and further preferably 0.7%.

[0233] [Method for measuring the chemical composition of hot-rolled steel sheets]

[0234] The chemical composition of the hot-rolled steel sheet of the present embodiment can be measured using the well-known component analysis method according to JIS G0321:2017. Specifically, chips are collected from the hot-rolled steel sheet using a cutting tool such as a drill. The collected chips are dissolved in an acid to obtain a solution. The solution is subjected to ICP-MAS (Inductively Coupled Plasma Mass Spectrometry) to perform elemental analysis of the chemical composition. The C content and the S content are determined using the well-known high-frequency combustion method (combustion-infrared absorption method). For the N content, the well-known inert gas melting-thermal conductivity method is used.

[0235] In addition, the content of each element is set to the minimum digit of each element content specified in the present embodiment by rounding off the decimal of the measured value based on the significant figures specified in the present embodiment. For example, the C content of the steel material of the present embodiment is specified with a value up to the third decimal place. Therefore, the C content is set to the value up to the third decimal place obtained by rounding off the fourth decimal place of the measured value.

[0236] The contents of other elements other than the C content of the steel material of the present embodiment are similarly obtained by rounding off the decimals of the numerical values ​​up to the minimum digit specified in the present embodiment with respect to the measured values.

[0237] In addition, rounding means that if the decimal is less than 5, it is discarded, and if the decimal is greater than 5, it is rounded up.

[0238] [Other technical features of the hot-rolled steel sheet of the present embodiment other than the chemical composition]

[0239] The content of each element in the chemical composition of the hot-rolled steel sheet according to the present embodiment is within the range of the present embodiment, and satisfies the following technical features 1 to 4.

[0240] Technical feature 1: The area ratio of bainitic ferrite in the microstructure is 85% or more.

[0241] Technical feature 2: Dislocation density is 8.0×10 13 / m 2 ~100.0×10 13 / m 2 .

[0242] Technical feature 3: The average circle equivalent diameter of Ti carbides in the hot-rolled steel sheet is 10 nm or less.

[0243] Technical feature 4: The average circle equivalent diameter of bainitic ferrite grains is less than 15 μm.

[0244] The following describes each technical feature.

[0245] [Technical feature 1: Area ratio of bainitic ferrite]

[0246] In the microstructure of the hot-rolled steel sheet of the present embodiment, the area ratio of bainitic ferrite is 85% or more. The microstructure of the hot-rolled steel sheet of the present embodiment may also be a bainitic ferrite single phase. In the case where the microstructure of the hot-rolled steel sheet of the present embodiment is composed of bainitic ferrite and other phases, the other phases are, for example, one or more selected from the group consisting of polygonal ferrite, pearlite, bainite, and cementite.

[0247] Bainitic ferrite can be distinguished from polygonal ferrite and bainite in the following respects.

[0248] [Difference between bainitic ferrite and polygonal ferrite]

[0249] Bainitic ferrite is a collection of grains with slightly different crystal orientations. Therefore, a contrast difference is confirmed within the grains. On the other hand, polygonal ferrite is a structure with almost no crystal orientation difference within the grains. Therefore, the inside of the grains is observed with a uniform contrast. Therefore, bainitic ferrite can be distinguished from polygonal ferrite based on the contrast caused by the crystal orientation difference.

[0250] [Difference between bainitic ferrite and bainite]

[0251] The crystal structure of bainitic ferrite is the same as that of bainite, which is a bcc structure. Therefore, it is difficult to distinguish bainitic ferrite from bainite based on the crystal structure. Moreover, it is difficult to distinguish bainitic ferrite from bainite based on the difference in crystal orientation. However, bainitic ferrite can be distinguished from bainite based on the presence or absence of Fe carbides in the grains and at the grain boundaries. Here, Fe carbides refer to carbides containing Fe, such as cementite.

[0252] Specifically, in bainitic ferrite, there are no Fe carbides in the grains and at the grain boundaries. On the other hand, in bainite, there are Fe carbides in the laths and / or at the lath boundaries. Therefore, bainitic ferrite can be distinguished from bainite based on the presence or absence of Fe carbides in the grains and at the grain boundaries.

[0253] [Effects of the area ratio of bainitic ferrite]

[0254] For the microstructure of the hot-rolled steel sheet whose contents of each element in the chemical composition are within the range of the present embodiment, if the area ratio of bainitic ferrite is 85% or more, higher strength and higher rigidity can be obtained on the premise of satisfying other technical features 2 to 4.

[0255] The lower limit of the area ratio of bainitic ferrite is preferably 88%, more preferably 90%, more preferably 92%, more preferably 94%, and still more preferably 96%.

[0256] [Method for measuring the area ratio of bainitic ferrite]

[0257] The area ratio of bainitic ferrite can be obtained as follows.

[0258] Microstructure observation was performed using a field emission scanning electron microscope (FE-SEM). Microstructure observation was performed using electron tunneling contrast imaging (ECCI). The observation conditions were set to an acceleration voltage of 20 kV, tilt (T) = 0°, and reflected electron mode. Electron backscatter diffraction (EBSD) was used to measure the crystal orientation.

[0259] The test piece was collected from the center of the hot-rolled steel plate width. The measurement position was set to a position where the distance from the surface of the test piece in the thickness direction of the hot-rolled steel plate was the thickness / 4 depth, the measurement range was set to 100 μm × 100 μm, and the measurement interval was set to 0.1 μm. The measurement range was set to include the longitudinal section in the L direction (the length direction of the hot-rolled steel plate) and the T direction (the thickness direction of the hot-rolled steel plate).

[0260] The measurement data was analyzed by the following procedure using analysis software to identify and quantify polygonal ferrite and bainitic ferrite.

[0261] (Sequence 1)

[0262] The area surrounded by grain boundaries of 15° or more is defined as one grain. In addition, when the equivalent circle diameter of the area surrounded by grain boundaries of 15° or more is less than 1.0 μm, the area is judged to be measurement noise and is not identified as a grain. In other words, the area judged to be measurement noise is excluded.

[0263] (Sequence 2)

[0264] The average value of the grain orientation difference in each grain (hereinafter referred to as GAM value) was calculated. Grains with a GAM value of 0.5° or less were defined as polygonal ferrite. Grains with a GAM value exceeding 0.5° were defined as bainitic ferrite.

[0265] In the above-mentioned microstructure observation, phases different from bainitic ferrite and polygonal ferrite (pearlite, bainite, cementite) can be easily distinguished by contrast.

[0266] The identified bainitic ferrite was quantified. The area ratio (%) of bainitic ferrite was calculated based on the area of ​​the quantified bainitic ferrite and the total area of ​​the measurement range (100 μm×100 μm). In addition, the area determined to be measurement noise was excluded from the total area of ​​the measurement range.

[0267] In addition, a well-known program may be used as the EBSD analysis program for obtaining the GAM value. For example, OIM Data Collection / Analysis 6.2.0 manufactured by TSL Solutions Co., Ltd. may be used.

[0268] [Technical feature 2: Dislocation density]

[0269] Furthermore, in the hot-rolled steel sheet of the present embodiment, the dislocation density is 8.0×10 13 / m 2 ~100.0×10 13 / m 2 .

[0270] If the dislocation density increases, the rigidity of the hot-rolled steel sheet increases. As described above, the strain of bainitic ferrite is higher than that of polygonal ferrite. Therefore, the dislocation density of bainitic ferrite is higher than that of polygonal ferrite. Therefore, in the microstructure of the hot-rolled steel sheet, if the area ratio of bainitic ferrite is 85% or more, the dislocation density is high and the strength of the hot-rolled steel sheet increases. However, even if the hot-rolled steel sheet whose content of each element in the chemical composition is within the range of the present embodiment satisfies Technical Features 1, 3 and 4, if the dislocation density is too low, the rigidity cannot become sufficiently high.

[0271] On the other hand, even if a hot-rolled steel sheet having a chemical composition with each element content within the range of the present embodiment satisfies Technical Features 1, 3, and 4, if the dislocation density is too high, the workability of the hot-rolled steel sheet is reduced.

[0272] If the content of each element in the chemical composition is within the range of the present embodiment, the dislocation density of the hot-rolled steel sheet is 8.0×10 13 / m 2 ~100.0×10 13 / m 2 , then on the premise of satisfying technical features 1, 3 and 4, excellent processability and excellent LME resistance can be obtained, and higher strength and higher rigidity can be obtained.

[0273] The preferred lower limit of dislocation density is 10.0×10 13 / m 2 , and more preferably 15.0×10 13 / m 2 , and more preferably 20.0×10 13 / m 2 .

[0274] The preferred upper limit of dislocation density is 90.0×10 13 / m 2 , and more preferably 80.0×10 13 / m 2 , and more preferably 70.0×10 13 / m 2 .

[0275] [Method for measuring dislocation density]

[0276] The dislocation density of the hot-rolled steel sheet according to the present embodiment can be obtained as follows.

[0277] A test piece for measuring dislocation density was collected from the center of the hot-rolled steel sheet in width. The size of the test piece was set to 20 mm in width×20 mm in length×sheet thickness.

[0278] The surface of the test piece was ground and polished with #80 to #1500 sandpaper from the surface to the plate thickness / 4 depth position to achieve mirror finish. In addition, the mirror-polished test piece was electrolytically polished for more than 50 μm in the plate thickness direction using 10 volume % perchloric acid (acetic acid solvent) to remove the strain of the surface layer of the test piece. The surface (observation surface) of the electrolytically polished test piece was measured by X-ray diffraction (XRD) to obtain the half-value width ΔK of the peaks of the (110), (211), and (220) planes of the body-centered cubic structure (bcc structure).

[0279] In XRD, the half-value width ΔK was measured with the radiation source set to CoKα line, the tube voltage set to 30 kV, and the tube current set to 100 mA. In order to measure the half-value width derived from the X-ray diffraction device, powder of LaB6 (lanthanum hexaboride) was used.

[0280] The non-uniform strain ε of the test piece is calculated from the half-value width ΔK calculated by the above method and the Williamson-Hall formula (formula (I)).

[0281] ΔK×cosθ / λ=0.9 / D+2ε×sinθ / λ(I)

[0282] In formula (I), θ is the diffraction angle (°), λ is the wavelength of X-rays (nm), and D is the crystallite size (nm).

[0283] Using the obtained inhomogeneous strain ε and formula (II), the dislocation density ρ ( / m 2 ).

[0284] ρ=14.4×ε 2 / b 2 (II)

[0285] Here, in formula (II), b is the Burgers vector of the body-centered cubic structure (iron) (b=0.248 (nm)).

[0286] [Technical feature 3: Average circle equivalent diameter of Ti carbides]

[0287] In the hot-rolled steel sheet of the present embodiment, the average equivalent circle diameter of the Ti carbides in the hot-rolled steel sheet is 10 nm or less. Here, the equivalent circle diameter refers to the diameter of a circle having the same area as the area of ​​the Ti carbides.

[0288] As described above, Ti carbides improve the strength of hot-rolled steel sheets due to precipitation strengthening. For hot-rolled steel sheets whose contents of each element in the chemical composition are within the range of the present embodiment, if the average equivalent circle diameter of Ti carbides exceeds 10 nm, the Ti carbides in the hot-rolled steel sheets are coarse. If the Ti carbides are coarse, sufficient precipitation strengthening cannot be obtained. As a result, the strength of the hot-rolled steel sheets is not high enough.

[0289] For the hot-rolled steel sheet whose content of each element in the chemical composition is within the range of the present embodiment, if the average circle equivalent diameter of Ti carbide is 10 nm or less, excellent workability and excellent LME resistance are maintained while satisfying other technical features 1, 2 and 4, while higher strength and higher rigidity can be obtained.

[0290] The upper limit of the average circle-equivalent diameter of Ti carbides is preferably 9 nm, more preferably 8 nm.

[0291] The lower limit of the average circle equivalent diameter of Ti carbides is not particularly limited, but the lower limit of the average circle equivalent diameter of Ti carbides is preferably 2 nm, more preferably 3 nm, more preferably 4 nm, and more preferably 5 nm.

[0292] [Method for measuring the average equivalent circle diameter of Ti carbides]

[0293] The average equivalent circle diameter of Ti carbides can be obtained by the following method. A sample of the plate thickness of the hot-rolled steel plate is collected from the center of the plate width of the hot-rolled steel plate. Grind the sample from both sides using sandpaper, and make a sample with a thickness of 50 μm centered at a position where the distance from the surface is the plate thickness / 4 depth. After that, a disc-shaped sample with a diameter of 3 mm is collected. The disc-shaped sample is immersed in a 10% perchloric acid-glacial acetic acid solution and electrolytic grinding is performed to make a film sample with a thickness of 100 nm.

[0294] The observation surface of the produced thin film sample was observed in five fields using a transmission electron microscope (TEM). The magnification was set to 600,000 times and each field of view was set to 200 nm×170 nm.

[0295] In each field of view, the precipitate is determined based on the contrast. The determined precipitate is subjected to a component analysis performed by EDS. The result of the analysis performed by EDS is that the precipitate in which Ti and C are detected is determined as Ti carbide. The equivalent circular diameter of each determined Ti carbide is obtained. The arithmetic mean of the equivalent circular diameters of all Ti carbides confirmed in 5 fields of view is defined as the average equivalent circular diameter (nm) of Ti carbides.

[0296] [Technical feature 4: Average circle equivalent diameter of bainitic ferrite grains]

[0297] In the microstructure of the hot-rolled steel sheet of the present embodiment, the average equivalent circle diameter of the crystal grains of bainitic ferrite is 15 μm or less. Here, the equivalent circle diameter refers to the diameter of a circle having the same area as the crystal grain.

[0298] The size of the grains of bainitic ferrite strongly affects rigidity. For a hot-rolled steel sheet whose content of each element in the chemical composition is within the range of the present embodiment, even if technical features 1 to 3 are satisfied, if the circle equivalent diameter of the grains of bainitic ferrite exceeds 15 μm, high strength, excellent workability, and excellent LME resistance can be obtained, but sufficient rigidity cannot be obtained.

[0299] For hot-rolled steel sheets whose contents of each element in the chemical composition are within the range of the present embodiment, if the average circle-equivalent diameter of the grains of bainitic ferrite is 15 μm or less, higher strength, excellent workability, and excellent LME resistance can be obtained, while satisfying other technical features 1 to 3, and higher rigidity can be obtained.

[0300] The upper limit of the average circle-equivalent diameter of the crystal grains of bainitic ferrite is preferably 14 μm, more preferably 13 μm, and further preferably 12 μm.

[0301] The lower limit of the average circle-equivalent diameter of the bainitic ferrite grains is not particularly limited, but the lower limit of the average circle-equivalent diameter of the bainitic ferrite grains is preferably 1 μm, more preferably 2 μm, more preferably 3 μm, and still more preferably 5 μm.

[0302] [Method for measuring the equivalent circle diameter of bainitic ferrite grains]

[0303] The equivalent circular diameter of the grains of bainitic ferrite of the hot-rolled steel sheet can be calculated as follows. The equivalent circular diameter of each grain of bainitic ferrite identified in the microstructure observation is calculated using the method described in the above-mentioned [Method for measuring the area ratio of bainitic ferrite]. The arithmetic mean of the obtained equivalent circular diameters is defined as the average equivalent circular diameter (μm) of the grains of bainitic ferrite. In addition, when the equivalent circular diameter of the area surrounded by grain boundaries of more than 15° is less than 1.0 μm, the area is judged to be measurement noise and is not identified as a grain. That is, when the equivalent circular diameter of the area surrounded by grain boundaries of more than 15° is less than 1.0 μm, the area is set as an exception.

[0304] As described above, the content of each element in the chemical composition of the hot-rolled steel sheet of the present embodiment is within the above range, and the hot-rolled steel sheet of the present embodiment also satisfies technical features 1 to 4. Therefore, the hot-rolled steel sheet has high strength, excellent workability, and, when a hot-dip galvanizing layer is formed on the surface of the hot-rolled steel sheet, excellent LME resistance, and high rigidity.

[0305] Specifically, in the hot-rolled steel sheet of the present embodiment, the tensile strength as an index of strength is 780 MPa or more, the total elongation as an index of workability is 14.0% or more, and the yield ratio as an index of rigidity is 85% or more.

[0306] The preferred lower limit of the tensile strength of the hot-rolled steel sheet is 785 MPa, more preferably 790 MPa, more preferably 795 MPa, and still more preferably 800 MPa. The upper limit of the tensile strength of the hot-rolled steel sheet is not particularly limited, and is, for example, 950 MPa.

[0307] The lower limit of the total elongation of the hot-rolled steel sheet is preferably 14.5%, more preferably 15.0%, and further preferably 15.5%. The upper limit of the total elongation of the hot-rolled steel sheet is not particularly limited, and is, for example, 20.0%.

[0308] The lower limit of the yield ratio of the hot-rolled steel sheet is preferably 86%, more preferably 87%, further preferably 88%, further preferably 89%.

[0309] [Measurement method of tensile strength, total elongation, and yield ratio]

[0310] The tensile strength, total elongation, and yield ratio of the hot-rolled steel sheet can be obtained by a tensile test in accordance with JIS Z2241:2011.

[0311] Specifically, a plate-shaped tensile test piece equivalent to the JIS No. 5 test piece specified in JIS Z2241: 2011 is collected from the center of the plate width of the hot-rolled steel plate. The length direction of the test piece is set to a direction orthogonal to the rolling direction of the hot-rolled steel plate. According to JIS Z2241: 2011, a tensile test is carried out at room temperature and in the atmosphere to obtain the yield strength YS, tensile strength TS, and total elongation T.EL. At this time, the 0.2% yield strength is defined as the yield strength YS (MPa). The yield ratio YR is obtained using the following formula using the obtained yield strength YS (MPa) and tensile strength TS (MPa).

[0312] Yield ratio YR = YS / TS

[0313] [Regarding Hot-Dip Plated Steel Sheet Using the Hot-Rolled Steel Sheet of the Embodiment]

[0314] The hot-dip galvanized steel sheet of the present embodiment comprises the hot-rolled steel sheet of the present embodiment described above and a hot-dip galvanized coating mainly containing Zn. The hot-dip galvanized coating is formed on the surface of the hot-rolled steel sheet. The hot-dip galvanized coating has a known structure. The hot-dip galvanized coating is described below.

[0315] [For hot-dip galvanizing]

[0316] As described above, the hot-dip galvanized coating mainly contains Zn. Specifically, the hot-dip galvanized coating contains 65.00% or more of Zn by mass%. The hot-dip galvanized coating may also be a layer formed by so-called hot-dip galvanizing (GI). Hot-dip galvanizing contains less than 1.00% of elements other than Zn by mass, with the remainder being Zn. If the Zn content of the hot-dip galvanized coating is 65.00% or more by mass, sufficient corrosion resistance can be obtained. The preferred lower limit of the Zn content of the hot-dip galvanized coating is 70.00%, and more preferably 73.00%.

[0317] [Chemical composition of hot-dip galvanizing coating]

[0318] The hot-dip galvanizing coating may have a chemical composition other than GI. The chemical composition of the hot-dip galvanizing coating is preferably within a well-known range. The chemical composition of the hot-dip galvanizing coating includes, for example, the following elements.

[0319] [Required elements]

[0320] Al: 0.05~35.00%

[0321] Aluminum (Al) is an easily oxidizable element and improves the corrosion resistance of the hot-dip galvanized coating by sacrificial corrosion protection. The above effect can be fully obtained when the Al content is 0.05 to 35.00%.

[0322] The preferred lower limit of the Al content is 0.08%, more preferably 0.10%, and more preferably 0.15%. The preferred upper limit of the Al content is 33.00%, more preferably 30.00%, more preferably 28.00%, more preferably 25.00%, more preferably 23.00%, and more preferably 21.00%.

[0323] The balance of the chemical composition of the hot-dip galvanizing layer of the present embodiment is Zn and impurities. Here, impurities refer to elements that are mixed from the raw materials when the hot-dip galvanizing treatment is performed, and are not intentionally contained.

[0324] [For any element]

[0325] The chemical composition of the hot-dip galvanizing layer of the present embodiment may further contain one or more elements selected from the following Group 1 to Group 7 in place of a portion of Zn. Group 1 to Group 7 will be described below.

[0326] [Group 1] Mg: 30.0% or less

[0327] [Second Group (Sn Group)] One or more selected from the group consisting of Sn: 2.00% or less, Bi: 2.00% or less, and In: 2.00% or less

[0328] [Group 3 (Ca Group)] One or more selected from the group consisting of Ca: 3.00% or less, Y: 3.00% or less, La: 3.00% or less, and Ce: 3.00% or less

[0329] [Group 4] Si: 2.50% or less

[0330] [Fifth Group (Cr Group)] One or more selected from the group consisting of Cr: 0.5% or less, Ti: 0.5% or less, Ni: 0.5% or less, Co: 0.5% or less, V: 0.5% or less, Nb: 0.5% or less, Cu: 0.5% or less, and Mn: 0.5% or less

[0331] [Group 6] Fe: 5.0% or less

[0332] [Group 7 (Sr Group)] One or more selected from the group consisting of Sr: 0.5% or less, Sb: 0.5% or less, Pb: 0.5% or less, and B: 0.5% or less

[0333] [Group 1 (Mg)]

[0334] Mg: 30.0% or less

[0335] Magnesium (Mg) is an arbitrary element, and Mg may not be contained. That is, the Mg content may be 0%.

[0336] Mg is an easily oxidizable element and improves the corrosion resistance of the hot-dip galvanized coating by sacrificial corrosion protection. As for the Mg content, as long as a small amount of Mg is contained, the above effect can be obtained to a certain extent.

[0337] However, if the Mg content is too high, even if the contents of other elements are within the ranges of the present embodiment, the oxidized dross increases. In this case, the appearance quality of the hot-dip plated steel sheet decreases.

[0338] Therefore, the Mg content is 0 to 30.0%, and when contained, the Mg content is 30.0% or less.

[0339] The lower limit of the Mg content is preferably greater than 0%, more preferably 0.1%, more preferably 0.5%, more preferably 1.0%, and still more preferably 2.0%.

[0340] The upper limit of the Mg content is preferably 25.0%, more preferably 20.0%, more preferably 15.0%, more preferably 10.0%, more preferably 8.0%, and still more preferably 7.0%.

[0341] [Group 2 (Sn, Bi, and In)]

[0342] One or more selected from the group consisting of Sn: 2.00% or less, Bi: 2.00% or less, and In: 2.00% or less,

[0343] Tin (Sn), bismuth (Bi), and indium (In) are arbitrary elements, and Sn, Bi, and In may not be contained. That is, the Sn content, Bi content, and In content may be 0%, respectively.

[0344] When the hot-dip galvanized coating contains Mg, these elements form intermetallic compounds with Mg. As a result, the corrosion resistance of the hot-dip galvanized steel sheet is improved. The above effect can be obtained to a certain extent as long as a small amount of Sn, Bi and In is contained.

[0345] However, if the content of these elements is too high, the viscosity of the hot-dip galvanizing bath increases even if the content of other elements is within the range of the present embodiment. In this case, the appearance quality of the hot-dip galvanized steel sheet decreases.

[0346] Therefore, the Sn content is 0 to 2.00%, the Bi content is 0 to 2.00%, and the In content is 0 to 2.00%. When contained, the Sn content is 2.00% or less, the Bi content is 2.00% or less, and the In content is 2.00% or less.

[0347] The lower limit of the content of each element is preferably greater than 0%, more preferably 0.01%, and further preferably 0.05%.

[0348] The upper limit of the content of each element is preferably 1.90%, more preferably 1.80%, and further preferably 1.70%.

[0349] [Group 3 (Ca, Y, La, and Ce)]

[0350] One or more selected from the group consisting of Ca: 3.00% or less, Y: 3.00% or less, La: 3.00% or less, and Ce: 3.00% or less,

[0351] Calcium (Ca), yttrium (Y), lanthanum (La), and selenium (Ce) are all arbitrary elements, and Ca, Y, La, and Ce may not be contained. That is, the content of these elements may be 0%.

[0352] These elements form intermetallic compounds with Al and Zn in the hot-dip galvanized layer. As a result, the corrosion resistance of the hot-dip galvanized steel sheet is improved. The above effects can be obtained to a certain extent as long as a small amount of these elements is contained.

[0353] However, if the content of these elements is too high, even if the content of other elements is within the range of the present embodiment, the oxidation dross increases. In this case, the appearance quality of the hot-dip plated steel sheet decreases.

[0354] Therefore, the Ca content is 0 to 3.00%, the Y content is 0 to 3.00%, the La content is 0 to 3.00%, and the Ce content is 0 to 3.00%. When contained, the Ca content is 3.00% or less, the Y content is 3.00% or less, the La content is 3.00% or less, and the Ce content is 3.00% or less.

[0355] The lower limit of the content of each element is preferably greater than 0%, more preferably 0.01%, more preferably 0.05%, and further preferably 0.10%.

[0356] The upper limit of the content of each element is preferably 2.80%, more preferably 2.50%, and further preferably 2.00%.

[0357] [Group 4 (Si)]

[0358] Si: 2.50% or less,

[0359] Silicon (Si) is an arbitrary element, and Si may not be contained. That is, the Si content may be 0%.

[0360] Si improves the corrosion resistance of hot-dip plated steel sheets. The above effect can be obtained to a certain extent even if a small amount of Si is contained.

[0361] However, if the Si content is too high, the viscosity of the hot-dip galvanizing bath increases even if the contents of other elements are within the ranges of the present embodiment. In this case, the appearance quality of the hot-dip galvanized steel sheet decreases.

[0362] Therefore, the Si content is 0 to 2.50%, and when contained, the Si content is 2.50% or less.

[0363] The lower limit of the Si content is preferably greater than 0%, more preferably 0.01%, further preferably 0.05%, further preferably 0.10%.

[0364] The upper limit of the Si content is preferably 2.00%, more preferably 1.50%, further preferably 1.00%, further preferably 0.50%.

[0365] [Group 5 (Cr, Ti, Ni, Co, V, Nb, Cu, and Mn)]

[0366] One or more selected from the group consisting of Cr: 0.5% or less, Ti: 0.5% or less, Ni: 0.5% or less, Co: 0.5% or less, V: 0.5% or less, Nb: 0.5% or less, Cu: 0.5% or less, and Mn: 0.5% or less,

[0367] Chromium (Cr), titanium (Ti), nickel (Ni), cobalt (Co), vanadium (V), niobium (Nb), copper (Cu), and manganese (Mn) are all arbitrary elements, and Cr, Ti, Ni, Co, V, Nb, Cu, and Mn may not be contained. That is, the content of these elements may be 0%.

[0368] These elements improve the appearance quality of hot-dip galvanized steel sheets. These elements also form intermetallic compounds with Al in hot-dip galvanized coatings. As a result, the corrosion resistance of hot-dip galvanized steel sheets is improved. As long as a small amount of these elements is contained, the above effects can be obtained to a certain extent.

[0369] However, if the content of these elements is too high, the viscosity of the hot-dip galvanizing bath increases even if the content of other elements is within the range of the present embodiment. In this case, the appearance quality of the hot-dip galvanized steel sheet decreases.

[0370] Therefore, the Cr content is 0-0.5%, the Ti content is 0-0.5%, the Ni content is 0-0.5%, the Co content is 0-0.5%, the V content is 0-0.5%, the Nb content is 0-0.5%, the Cu content is 0-0.5%, and the Mn content is 0-0.5%. When contained, the Cr content is 0.5% or less, the Ti content is 0.5% or less, the Ni content is 0.5% or less, the Co content is 0.5% or less, the V content is 0.5% or less, the Nb content is 0.5% or less, the Cu content is 0.5% or less, and the Mn content is 0.5% or less.

[0371] The lower limit of the content of each element is preferably greater than 0%, and more preferably 0.1%.

[0372] The upper limit of the content of each element is preferably less than 0.5%, and more preferably 0.4%.

[0373] [Group 6 (Fe)]

[0374] Fe: 5.0% or less,

[0375] Iron (Fe) is an arbitrary element, and Fe may not be contained. In other words, the Fe content may be 0%.

[0376] Fe increases the hardness of the hot-dip galvanized layer and improves the workability of the hot-dip galvanized steel sheet. The above effects can be obtained to a certain extent even if a small amount of Fe is contained.

[0377] However, if the Fe content is too high, the hardness of the hot-dip galvanized layer becomes too high even if the contents of other elements are within the ranges of the present embodiment. In this case, the workability of the hot-dip galvanized steel sheet is reduced.

[0378] Therefore, the Fe content is 0 to 5.0%, and when contained, the Fe content is 5.0% or less.

[0379] The lower limit of the Fe content is preferably greater than 0%, more preferably 0.1%, and further preferably 0.5%.

[0380] The upper limit of the Fe content is preferably 4.5%, more preferably 4.0%, and further preferably 3.5%.

[0381] [Group 7 (Sr, Sb, Pb, and B)]

[0382] One or more selected from the group consisting of Sr: 0.5% or less, Sb: 0.5% or less, Pb: 0.5% or less, and B: 0.5% or less,

[0383] Strontium (Sr), antimony (Sb), lead (Pb), and boron (B) are all arbitrary elements, and Sr, Sb, Pb, and B may not be contained. That is, the content of these elements may be 0%.

[0384] These elements improve the metallic luster of the hot-dip galvanized coating and improve the appearance quality of the hot-dip galvanized steel sheet. The above effects can be achieved to a certain extent as long as a small amount of these elements is contained.

[0385] However, if the content of these elements is too high, even if the content of other elements is within the range of the present embodiment, the oxidation dross increases. In this case, the appearance quality of the hot-dip plated steel sheet decreases.

[0386] Therefore, the Sr content is 0 to 0.5%, the Sb content is 0 to 0.5%, the Pb content is 0 to 0.5%, and the B content is 0 to 0.5%. When contained, the Sr content is 0.5% or less, the Sb content is 0.5% or less, the Pb content is 0.5% or less, and the B content is 0.5% or less.

[0387] The lower limit of the content of each element is preferably greater than 0%, and more preferably 0.1%.

[0388] The upper limit of the content of each element is preferably less than 0.5%, and more preferably 0.4%.

[0389] [Method for measuring the chemical composition of hot-dip galvanized coating]

[0390] The chemical composition of the hot-dip galvanized coating can be obtained by the following method. The hot-dip galvanized coating is dissolved using hydrochloric acid containing an inhibitor. The inhibitor can be, for example, IBIT manufactured by Asahi Chemical Industry Co., Ltd. The elemental analysis of the solution is performed in the same manner as the chemical composition analysis of the hot-rolled steel sheet described above. The chemical composition of the hot-dip galvanized coating can be obtained by the above method.

[0391] The hot-dip plated steel sheet having the above hot-rolled steel sheet and the hot-dip galvanized steel sheet has not only high strength, high rigidity and excellent workability, but also excellent LME resistance.

[0392] [Method for producing hot-rolled steel sheet]

[0393] An example of a method for manufacturing a hot-rolled steel sheet according to the present embodiment is described. The method for manufacturing a hot-rolled steel sheet described below is an example for manufacturing a hot-rolled steel sheet according to the present embodiment. Therefore, the hot-rolled steel sheet having the above-mentioned structure can also be manufactured by other manufacturing methods other than the manufacturing method described below. However, the manufacturing method described below is a preferred example of the method for manufacturing a hot-rolled steel sheet according to the present embodiment.

[0394] An example of the method for producing a hot-rolled steel sheet according to the present embodiment includes the following steps.

[0395] (Process 1) Blank preparation process

[0396] (Process 2) Hot rolling process

[0397] (Process 3) Cooling process

[0398] (Process 4) Coil-up process

[0399] Furthermore, the manufacturing method is implemented using a production line device. The production line device includes a heating furnace, a roughing mill, a finishing mill, a run-out table cooling equipment, and a down coiler in order from upstream to downstream. A plurality of conveying rollers are arranged between the devices.

[0400] In the above-mentioned manufacturing process, the main manufacturing conditions are as follows.

[0401] (Process 2) Hot rolling process

[0402] Finishing temperature FT: 850℃~950℃

[0403] (Process 3) Cooling process

[0404] Front cooling rate CR1: less than 25℃ / sec

[0405] ·Switching temperature ST from front stage cooling speed to rear stage cooling speed: 730℃~830℃

[0406] ·Back stage cooling rate CR2: 25℃ / sec or more

[0407] (Process 4) Coil-up process

[0408] Coiling temperature CT: 470℃~620℃

[0409] Hereinafter, each step will be described.

[0410] [(Process 1) Blank preparation process]

[0411] In the billet preparation step, a billet having a content of each element in the chemical composition within the range of the present embodiment is prepared. The billet is manufactured, for example, by the following method. Molten steel having a content of each element in the chemical composition within the range of the present embodiment is manufactured. The above-mentioned molten steel is used to manufacture a billet (slab or ingot) by a casting method. For example, the above-mentioned molten steel is used to manufacture a slab by a well-known continuous casting method. Alternatively, the above-mentioned molten steel is used to manufacture an ingot by a well-known ingot casting method.

[0412] [(Process 2) Hot rolling process]

[0413] The prepared billet (slab or ingot) is subjected to hot rolling to produce a steel plate. The hot rolling process includes a rough rolling process of rough rolling the billet to produce a rough bar (intermediate steel plate) and a finish rolling process of finish rolling the rough bar to produce a steel plate.

[0414] In the rough rolling process, the billet (slab or ingot) is heated in a heating furnace. The heated billet is rolled using a rough rolling mill to produce a rough bar. The heating temperature of the billet in the rough rolling process is, for example, 1250°C to 1300°C. The time that the billet is in the heating furnace is more than 30 minutes, preferably more than 60 minutes. The upper limit of the time in the furnace is not particularly limited, for example, 240 minutes.

[0415] In the finishing process, the rough bar is further rolled (finished) using a finishing mill to produce a steel plate. The finishing mill includes a plurality of rolling mills arranged in a row. Each rolling mill has a pair of working rolls. The surface temperature of the steel plate at the exit side of the rolling mill that last presses the steel plate among the plurality of rolling mills of the finishing mill is defined as the finishing temperature FT (°C). In the present embodiment, the finishing temperature FT is set as follows.

[0416] Finishing temperature FT: 850℃~950℃

[0417] [Finish rolling temperature FT: 850℃~950℃]

[0418] If the finishing temperature FT exceeds 950°C, the austenite grains in the steel sheet become excessively coarse during the finishing rolling process. Therefore, the grains of bainite ferrite in the manufactured hot-rolled steel sheet become coarse. On the other hand, if the finishing temperature FT is less than 850°C, excessive load is applied to the rolling mill.

[0419] When the finish rolling temperature FT is 850° C. to 950° C., the average circle-equivalent diameter of bainitic ferrite in the produced hot-rolled steel sheet becomes 15 μm or less, provided that other production conditions are satisfied.

[0420] [(Step 3) Cooling Step]

[0421] In the cooling process, a cooling device is used to rapidly cool the steel plate after the finish rolling. Specifically, for the steel plate after the finish rolling, for example, cooling in the cooling device is started within 3 seconds after the finish rolling is completed from the viewpoint of productivity. In the cooling device, a cooling medium is used to cool the steel plate. The cooling medium is, for example, water.

[0422] The cooling speed of the steel plate is different on the upstream side and the downstream side of the cooling device. The manufacturing conditions in the cooling process using the cooling device are as follows.

[0423] Front cooling rate CR1: less than 25℃ / sec

[0424] ·Switching temperature ST from front stage cooling speed to rear stage cooling speed: 730℃~830℃

[0425] ·Back stage cooling rate CR2: 25℃ / sec or more

[0426] Here, the period from the start of cooling by the cooling equipment until the steel sheet temperature reaches the switching temperature ST is called the "front cooling period", and the period from the switching temperature ST until the steel sheet temperature reaches the coiling temperature CT is called the "rear cooling period".

[0427] In the cooling process of the present embodiment, during the front cooling period, the recrystallization of austenite of the steel plate is promoted to form fine austenite recrystallization. Thus, the austenite non-recrystallized region in the steel plate is minimized, and the microstructure of the steel plate is made into a structure formed by fine austenite recrystallized grains. Furthermore, during the rear cooling period, the fine austenite is transformed into bainitic ferrite. The above-mentioned manufacturing conditions (front cooling rate CR1, switching temperature ST, rear cooling rate CR2) are described below.

[0428] [Front stage cooling rate CR1: less than 25°C / sec]

[0429] In the cooling process, first, the steel plate after the finish rolling is cooled at the front cooling rate CR1. That is, during the front cooling period, the steel plate is cooled at the front cooling rate CR1. If the front cooling rate CR1 is 25°C / s or more, at the moment when the steel plate temperature reaches the switching temperature ST (°C), an austenite non-recrystallized area remains in the steel plate. The austenite non-recrystallized area is easy to become polygonal ferrite during the rear cooling period. Therefore, for the hot-rolled steel plate after manufacturing, the area ratio of bainitic ferrite becomes lower. Moreover, in this case, the dislocation density also becomes lower.

[0430] If the front-stage cooling rate CR1 is less than 25°C / sec, the recrystallization of austenite can be promoted. Therefore, the austenite non-recrystallized region in the steel sheet can be reduced. As a result, in the microstructure of the hot-rolled steel sheet, the area ratio of bainitic ferrite can be increased, and the dislocation density can be set to an appropriate range.

[0431] The front-stage cooling rate CR1 is calculated using the following formula using the finishing temperature FT (°C), the switching temperature ST (°C), the rolling speed V1 (m / s) of the steel plate at the exit side of the rolling mill that finally presses down the steel plate, and the distance L1 (m) between the thermometer of the finishing temperature FT and the thermometer of the switching temperature ST.

[0432] CR1=(FT-ST) / (L1 / V)

[0433] The upper limit of the front-stage cooling rate CR1 is preferably 24° C. / sec, more preferably 23° C. / sec.

[0434] The lower limit of the front-stage cooling rate CR1 is not particularly limited. However, if the front-stage cooling rate CR1 is too slow, the production efficiency will be significantly reduced. Therefore, the preferred lower limit of the front-stage cooling rate CR1 is 5° C. / sec.

[0435] [Switching temperature ST: 730℃~830℃]

[0436] In the cooling device, the temperature of the steel sheet when the cooling rate is switched from the front-stage cooling rate CR1 to the rear-stage cooling rate CR2 is defined as a switching temperature ST (° C.).

[0437] When the switching temperature ST is higher than 830° C., the recrystallization of austenite is accelerated and the austenite is coarsened. As a result, the grains of bainitic ferrite in the hot-rolled steel sheet are coarsened.

[0438] On the other hand, if the switching temperature ST is lower than 730°C, the recrystallization of austenite is not completed during the first cooling period, and the austenite non-recrystallized region remains during the second cooling period. In this case, polygonal ferrite is generated in the hot-rolled steel sheet during the second cooling period. As a result, the area ratio of bainitic ferrite in the hot-rolled steel sheet decreases. Moreover, in this case, the dislocation density also decreases.

[0439] If the switching temperature ST is 730° C. to 830° C., the first cooling period is appropriate. Therefore, the recrystallization of austenite in the steel sheet can be sufficiently promoted, and cooling at the second cooling rate CR2 can be started after the austenite non-recrystallized region is sufficiently reduced.

[0440] The upper limit of the switching temperature ST is preferably 820°C, more preferably 810°C.

[0441] The lower limit of the switching temperature ST is preferably 740°C, more preferably 750°C.

[0442] [Back stage cooling rate CR2: 25°C / sec or more]

[0443] After the temperature of the steel sheet decreases to the switching temperature ST during the front cooling period, cooling at the rear cooling rate CR2 (rear cooling period) is started. If the rear cooling rate CR2 is less than 25°C / sec, the cooling rate during the rear cooling period is too slow. In this case, polygonal ferrite is generated in the hot-rolled steel sheet during the rear cooling period. As a result, the area ratio of bainitic ferrite in the hot-rolled steel sheet decreases. Moreover, the dislocation density decreases. Moreover, Ti carbides become coarse.

[0444] If the cooling rate CR2 of the latter stage is 25°C / sec or more, the cooling rate during the latter stage cooling is sufficiently fast. Therefore, on the premise of satisfying other manufacturing conditions, the area ratio of bainitic ferrite in the hot-rolled steel sheet becomes 85% or more, and the average equivalent circle diameter of the grains of bainitic ferrite becomes 15 μm or less.

[0445] The rear-stage cooling rate CR2 is calculated using the following formula using the switching temperature ST (°C), the coiling temperature CT (°C), the rolling speed V (m / s) of the steel plate at the exit side of the rolling mill that finally presses down the steel plate, and the distance L2 (m) between the thermometer of the switching temperature ST and the thermometer of the coiling temperature CT.

[0446] CR2=(ST-CT) / (L2 / V)

[0447] The preferable lower limit of the latter stage cooling rate CR2 is 30° C. / sec.

[0448] The upper limit of the latter stage cooling rate CR2 is not particularly limited. In consideration of equipment capacity, the upper limit of the latter stage cooling rate CR2 is preferably 70° C. / sec.

[0449] [(Process 4) Coil-up process]

[0450] In the coiling process, the steel plate that has passed through the cooling device is coiled into a coil by a coiling device. In the coiling process, Ti carbides are generated in the steel plate. Here, the surface temperature of the steel plate at the beginning of coiling is defined as the coiling temperature CT (°C). The coiling temperature CT affects the average circle equivalent diameter of Ti carbides. The coiling temperature CT also affects the microstructure of the hot-rolled steel plate (the ratio of bainitic ferrite, polygonal ferrite, and bainite). Therefore, the coiling temperature CT is adjusted to the following range.

[0451] Coiling temperature CT: 470℃~620℃

[0452] [Coiling temperature CT: 470℃~620℃]

[0453] When the coiling temperature CT is higher than 620°C, the end temperature of the latter cooling period in the cooling process is too high. In this case, for the microstructure in the steel sheet, coiling begins before the phase transformation from austenite to bainitic ferrite is completed. Therefore, part of the austenite is transformed into polygonal ferrite. As a result, the area ratio of bainitic ferrite in the hot-rolled steel sheet decreases. Moreover, the dislocation density also decreases. If the coiling temperature CT is higher than 620°C, the Ti carbides in the hot-rolled steel sheet are further coarsened.

[0454] On the other hand, if the coiling temperature CT is lower than 470° C., the end temperature of the second cooling period in the cooling process is too low. In this case, bainite is generated in the hot-rolled steel sheet. Therefore, the area ratio of bainitic ferrite in the hot-rolled steel sheet decreases.

[0455] When the coiling temperature CT is 470° C. to 620° C., the area ratio of bainitic ferrite in the microstructure of the hot-rolled steel sheet becomes 85% or more, provided that other manufacturing conditions are satisfied, and the average equivalent circle diameter of Ti carbides becomes 10 nm or less.

[0456] The hot-rolled steel sheet of the present embodiment is manufactured by the above manufacturing process. As described above, the hot-rolled steel sheet of the present embodiment can also be manufactured by other manufacturing methods other than the above manufacturing method. As long as the content of each element in the chemical composition of the hot-rolled steel sheet of the present embodiment is within the range of the present embodiment and has technical features 1 to 4, the manufacturing method thereof is not particularly limited.

[0457] [Other steps in the method for producing hot-rolled steel sheet]

[0458] The manufacturing method of the hot-rolled steel sheet of the present embodiment may also include other processes in addition to the above-mentioned processes. For example, the temper rolling process may be performed after the cooling process and before the coiling process, or after the coiling process. In the temper rolling process, the hot-rolled steel sheet is subjected to temper rolling. The temper rolling process is used to adjust the shape of the hot-rolled steel sheet, or to adjust the surface roughness, or to adjust the yield strength. The plate thickness reduction rate in the temper rolling process that can effectively obtain the above-mentioned effects is, for example, 0.1% or more. The preferred upper limit of the plate thickness reduction rate in the temper rolling process is 3.0%. In this case, the introduction of excessive strain into the hot-rolled steel sheet can be suppressed, and good ductility, bendability and flangeability can be maintained.

[0459] [Method for producing hot-dip plated steel sheet including hot-rolled steel sheet of the present embodiment]

[0460] The hot-dip plated steel sheet including the hot-rolled steel sheet according to the present embodiment can be produced by performing the following well-known hot-dip plating treatment process.

[0461] [Hot dip coating process]

[0462] In the hot-dip plating process, a hot-dip galvanized coating having the above-mentioned chemical composition is formed on the surface of the hot-rolled steel sheet. Specifically, a plating bath is prepared. The composition of the plating bath is adjusted according to the composition of the hot-dip galvanized coating to be formed. After the hot-rolled steel sheet is immersed in the plating bath for a certain period of time, the hot-rolled steel sheet is lifted out of the plating bath by a well-known method. For example, a sinking roller is arranged in the plating bath. The hot-rolled steel sheet immersed in the plating bath is turned to the upper direction by the sinking roller.

[0463] A hot-dip galvanizing coating is attached to the surface of the hot-rolled steel sheet lifted out of the plating bath. The amount of hot-dip galvanizing coating attached to the hot-rolled steel sheet is adjusted by a well-known gas purge device. The hot-dip galvanizing coating attached to the hot-rolled steel sheet lifted out of the plating bath solidifies to form a hot-dip galvanizing coating layer. The hot-dip galvanized steel sheet is manufactured by the above process.

[0464] [Other steps in the method for producing hot-dip coated steel sheet]

[0465] The manufacturing method of the hot-dip plated steel sheet of the present embodiment may also include other manufacturing processes in addition to the hot-dip plating process. For example, the manufacturing method of the hot-dip plated steel sheet of the present embodiment may also include a pre-Ni plating process before the hot-dip plating process. In the pre-Ni plating process, Ni plating is performed on the hot-rolled steel sheet to form a Ni plating layer on the surface of the hot-rolled steel sheet. The hot-dip plating process is performed on the hot-rolled steel sheet with the Ni plating layer formed thereon. In this case, the adhesion of the hot-dip galvanized coating to the hot-rolled steel sheet is improved.

[0466] Alternatively, the method for manufacturing a hot-dip galvanized steel sheet of the present embodiment may further include a chemical conversion treatment step after the hot-dip galvanizing step. In the chemical conversion treatment step, the manufactured hot-dip galvanized steel sheet is subjected to a chemical conversion treatment to form a chemical conversion film on the hot-dip galvanized coating. When the chemical conversion treatment step is performed, the method of the chemical conversion treatment is not particularly limited, and a well-known method is preferred. For example, a well-known chromium chemical conversion film may be formed as the chemical conversion film.

[0467] Alternatively, the method for manufacturing a hot-dip plated steel sheet of the present embodiment may further include performing a temper rolling process after the hot-dip plated treatment process. In the temper rolling process, the manufactured hot-dip plated steel sheet is subjected to temper rolling. When the above-mentioned chemical conversion treatment process is performed, the adhesion of the chemical conversion film can be improved by performing the temper rolling process before the chemical conversion treatment process. The preferred plate thickness reduction rate in the temper rolling process is 0.1 to 3.0%.

[0468] The method for manufacturing a hot-dip plated steel sheet may further include other manufacturing steps. The above-mentioned manufacturing method is an example of a manufacturing method for obtaining a hot-dip plated steel sheet of the present embodiment. Therefore, the method for manufacturing a hot-dip plated steel sheet of the present embodiment is not limited to the above-mentioned manufacturing method.

[0469] Example

[0470] The effects of one mode of the hot-rolled steel sheet and the hot-dip-plated steel sheet of the present embodiment will be further specifically described using examples. The conditions in the following examples are one condition example adopted to confirm the feasibility and effects of the hot-rolled steel sheet and the hot-dip-plated steel sheet of the present embodiment. Therefore, the hot-rolled steel sheet and the hot-dip-plated steel sheet of the present embodiment are not limited to this one condition example.

[0471] Hot-rolled steel sheets having the chemical compositions shown in Table 1 were produced.

[0472] [Table 1]

[0473] Table 1

[0474]

[0475] “-” in Table 1 indicates that the corresponding element content is 0% when the decimal of the measured numerical value is rounded off based on the significant figures specified in this embodiment.

[0476] For example, the Nb content of Test No. 1 is rounded off to the third decimal place and is 0%. The Cr content of Test No. 1 is rounded off to the second decimal place and is 0%.

[0477] Specifically, molten steel was continuously cast to produce slabs. The slabs were subjected to hot working processes (rough rolling process and finish rolling process). The slabs were heated at 1250°C to 1300°C for 60 minutes. The heated slabs were rolled using a rough rolling mill to produce rough bars. Then, the rough bars were rolled using a finishing mill to produce steel plates. The finishing rolling temperature FT (°C) of each test number is as shown in the "FT (°C)" column of Table 2.

[0478] [Table 2]

[0479] Table 2

[0480]

[0481] The steel plate after finish rolling was subjected to a cooling process. Specifically, in any test number, cooling using a cooling device was started within 2 seconds after the completion of finish rolling. The front-stage cooling rate CR1 (°C / second), the switching temperature ST (°C), and the rear-stage cooling rate CR2 (°C / second) of each test number in the cooling process are shown in "CR1 (°C / second)", "ST (°C)", and "CR2 (°C / second)" in Table 2, respectively.

[0482] The steel sheet that passed through the cooling device was coiled into a coil by a coiling device. The coiling temperature CT (°C) of each test number is shown in Table 2. The coiled steel sheet was naturally cooled to room temperature to produce the hot-rolled steel sheet of each test number shown in Table 1. The thickness of the hot-rolled steel sheet was 2.3 mm.

[0483] [Evaluation test]

[0484] The following evaluation tests were performed on the hot-rolled steel sheets of each test number.

[0485] (Test 1) Test for measuring the area ratio of bainitic ferrite and the average equivalent circle diameter of bainitic ferrite grains

[0486] (Test 2) Test for measuring the average equivalent circle diameter of Ti carbides

[0487] (Test 3) Dislocation density measurement test

[0488] (Test 4) Mechanical properties evaluation test

[0489] (Test 5) LME resistance evaluation test of hot-dip plated steel sheet

[0490] Hereinafter, Tests 1 to 5 will be described.

[0491] [(Test 1) Test for measuring the area ratio of bainitic ferrite and the average equivalent circle diameter of bainitic ferrite grains]

[0492] For each hot-rolled steel sheet of the test number, the area ratio (%) of bainitic ferrite and the average equivalent circle diameter (μm) of the bainitic ferrite grains were obtained by the methods described in the above-mentioned [Method for measuring the area ratio of bainitic ferrite] and [Method for measuring the equivalent circle diameter of the grains of bainitic ferrite]. The obtained area ratio of bainitic ferrite is shown in the "BF area ratio (%)" column in Table 3. In addition, the obtained average equivalent circle diameter of the grains of bainitic ferrite is shown in the "BF grain size (μm)" column in Table 3.

[0493] [Table 3]

[0494] Table 3

[0495]

[0496] [(Test 2) Test for measuring the average equivalent circle diameter of Ti carbides]

[0497] The average equivalent circle diameter of Ti carbides of the hot-rolled steel sheets of each test number was determined by the method described in [Method for measuring the average equivalent circle diameter of Ti carbides]. The obtained average equivalent circle diameter of Ti carbides is shown in the "TiC particle size (nm)" column in Table 3.

[0498] [(Test 3) Dislocation density measurement test]

[0499] The dislocation density of the hot-rolled steel sheet of each test number was determined by the method described in the above-mentioned [Method for measuring dislocation density]. The obtained dislocation density is shown in the “Dislocation density (×10 13 / m 2 )"column.

[0500] [(Test 4) Mechanical properties evaluation test]

[0501] The tensile strength TS, yield ratio YR, and total elongation T.EL of the hot-rolled steel sheet of each test number were obtained by a tensile test in accordance with JIS Z2241:2011.

[0502] Specifically, a plate-shaped tensile test piece equivalent to the JIS No. 5 test piece specified in JIS Z2241: 2011 was collected from the center of the plate width of the hot-rolled steel plate of each test number. The length direction of the test piece was set to a direction orthogonal to the rolling direction of the hot-rolled steel plate. According to JIS Z2241: 2011, a tensile test was carried out at room temperature and in the atmosphere to obtain the yield strength YS, tensile strength TS, and total elongation T.EL. The 0.2% yield strength is defined as the yield strength YS (MPa). The yield ratio YR is obtained using the following formula using the obtained yield strength YS (MPa) and tensile strength TS (MPa).

[0503] Yield ratio YR = YS / TS

[0504] The obtained yield strength YS (MPa), tensile strength TS (MPa), yield ratio YR (%), and total elongation T.EL (%) are shown in the "YS (MPa)", "TS (MPa)", "YR (%)", and "T.EL (%)" columns of Table 3.

[0505] [(Test 5) Evaluation test of LME resistance of hot-dip plated steel sheet]

[0506] [Manufacture of hot-dip galvanized steel sheets]

[0507] In order to evaluate the LME resistance of the hot-dip plated steel sheet, first, a hot-dip plated steel sheet was manufactured using the hot-rolled steel sheet of each test number. Specifically, the hot-rolled steel sheet of each test number was subjected to a well-known hot-dip treatment to form a hot-dip galvanized coating having a chemical composition shown in Table 4 on the surface of the hot-rolled steel sheet. The "Plating Number" column of "Plated Steel Sheet" in Table 5 shows the plating number of the hot-dip galvanized coating formed on the hot-rolled steel sheet of each test number. The plating number shown in the "Plating Number" column of "Plated Steel Sheet" in Table 5 is equivalent to the plating number of Table 4. The hot-dip plated steel sheet was manufactured using the above manufacturing process.

[0508] [Table 4]

[0509] Table 4

[0510]

[0511] [Table 5]

[0512] Table 5

[0513]

[0514] In addition, the element symbol written on the left side of the numerical value in Table 4 represents the element contained. For example, in the plating number P2, it is shown that 0.30% of Sn is contained as an element of the Sn group in terms of mass%.

[0515] The LME resistance of the hot-dip plated steel sheets of the manufactured test numbers was evaluated by the following method.

[0516] A sample steel plate of 100 mm × 75 mm × plate thickness was collected from the hot-dip galvanized steel plate of each test number. Figure 1 Specifically, a cylindrical boss member 1 having a diameter of 20 mm and a length of 25 mm was prepared. The boss member 1 was made of a steel material equivalent to SS400 specified in JIS G3101:2015.

[0517] like Figure 1As shown, the boss member 1 is arranged at the center of the sample steel plate 2 in such a manner that the axial direction of the boss member 1 becomes the normal direction of the surface of the sample steel plate 2. The arranged boss member 1 is welded to the sample steel plate 2 by arc welding. The welding wire is YGW12 specified in JIS Z3312:2009. In the arc welding, the weld bead 3 is rotated clockwise around the boss member 1 from the welding starting point when viewed from above. After passing the welding starting point, the arc welding is further continued until the overlapping area 4 of the weld bead is formed. The width of the overlapping area 4 is about 15 mm.

[0518] The current value during arc welding was set to 190 A, and the voltage value was set to 23 V. The welding speed was set to 0.3 m / min. As the shielding gas during arc welding, a mixed gas of 20 volume % CO2 gas and 80 volume % argon gas was used. The shielding gas flow rate during arc welding was set to 20 L / min.

[0519] In implementation Figure 1 Before arc welding, as shown Figure 2 As shown, the sample steel plate 2 and the restraining plate 5 are pre-joined. The restraining plate 5 is 120 mm × 95 mm × 4 mm thick and is set to be a steel plate equivalent to SS400 specified in JIS G3101: 2015. The sample steel plate 2 is arranged on the surface of the restraining plate 5. The entire circumference of the arranged sample steel plate 2 is welded to the restraining plate 5. The welding wire and welding conditions are set to be the same as the case of welding the boss member 1 to the sample steel plate 2.

[0520] In implementation Figure 1 Before welding the boss components, Figure 2 As shown in the figure, the sample steel plate 2 circumferentially welded to the restraining plate 5 is arranged on the stand 6, and the sample steel plate 2 and the restraining plate 5 are fixed to the stand 6 by a clamp not shown. After the sample steel plate 2 is fixed to the stand 6 by the clamp, Figure 1 As shown, the boss member 1 is welded to the sample steel plate 2 by arc welding.

[0521] After the boss member 1 is arc welded to the sample steel plate 2, Figure 1As shown, the boss member 1, the sample steel plate 2, and the restraining plate 5 are cut by a section 7 passing through the central axis of the boss member 1 and through the overlapping area 4 of the weld bead 3. In addition, the section 7 is observed at a magnification of 100 times using an optical microscope. During the observation, the presence or absence of cracks (molten metal embrittlement cracks) in the sample steel plate is visually confirmed. In the case where cracks are observed, the crack length is measured. The maximum crack length among the measured crack lengths is determined. If the maximum crack length is within 1.0 mm, it is judged that the LME resistance is excellent (indicated by "E" (excellent) in the "LME resistance evaluation" column of Table 5). On the other hand, if the maximum crack length exceeds 1.0 mm, it is judged that the LME resistance is low (indicated by "B" (poor) in the "LME resistance evaluation" column of Table 5).

[0522] [Evaluation results]

[0523] Referring to Tables 1 to 5, the contents of each element in the chemical composition of the hot-rolled steel sheets of Test Nos. 1 to 29 are appropriate. Moreover, the area ratio of bainitic ferrite in the hot-rolled steel sheets of Test Nos. 1 to 29 is 85% or more, and the average equivalent circle diameter of the grains of bainitic ferrite is 15 μm or less. Moreover, the average equivalent circle diameter of Ti carbides in the hot-rolled steel sheets of Test Nos. 1 to 29 is 10 nm or less, and the dislocation density is 8.0×10 13 / m 2 ~100.0×10 13 / m 2 Therefore, in the hot-rolled steel sheets of test numbers 1 to 29, the tensile strength TS is 780 MPa or more. Moreover, the yield ratio YR is 85% or more, showing excellent rigidity. Moreover, the total elongation T.EL is 14.0% or more, showing excellent workability (ductility).

[0524] On the other hand, in test number 30, the C content was too high. Therefore, polygonal ferrite was generated in the microstructure of the hot-rolled steel sheet, and the area ratio of bainitic ferrite was less than 85%. Moreover, the average circle equivalent diameter of bainitic ferrite exceeded 15 μm. Moreover, the dislocation density of the hot-rolled steel sheet was less than 8.0×10 13 / m 2 Therefore, the yield ratio YR is less than 85%, and sufficient rigidity cannot be obtained.

[0525] In test No. 31, the C content was too low. Therefore, the dislocation density of the hot-rolled steel sheet exceeded 100.0×10 13 / m 2 Therefore, the total elongation T.EL is less than 14.0%, and sufficient workability cannot be obtained. In addition, the tensile strength TS of the hot-rolled steel sheet is less than 780 MPa, and sufficient strength cannot be obtained.

[0526] In test No. 32, the Si content was too high. Therefore, polygonal ferrite was generated in the microstructure of the hot-rolled steel sheet, and the area ratio of bainitic ferrite was less than 85%. In addition, the average equivalent circle diameter of bainitic ferrite exceeded 15 μm. In addition, the dislocation density of the hot-rolled steel sheet was less than 8.0×10 13 / m 2 Therefore, the yield ratio YR is less than 85%, and sufficient rigidity cannot be obtained.

[0527] In test number 33, the Mn content was too high. Therefore, bainite was generated in the microstructure of the hot-rolled steel sheet, and the area ratio of bainitic ferrite was less than 85%. In addition, the dislocation density of the hot-rolled steel sheet exceeded 100.0×10 13 / m 2 Therefore, the total elongation T.EL is less than 14.0%, and sufficient processability cannot be obtained.

[0528] In test number 34, the Ti content was too low. Therefore, polygonal ferrite was generated in the microstructure of the hot-rolled steel sheet, and the area ratio of bainitic ferrite was less than 85%. In addition, the average circle equivalent diameter of bainitic ferrite exceeded 15 μm. In addition, the dislocation density of the hot-rolled steel sheet was less than 8.0×10 13 / m 2 Therefore, when YR is less than 85%, sufficient rigidity cannot be obtained.

[0529] In test number 35, the Ti content was too high. Therefore, the dislocation density of the hot-rolled steel sheet exceeded 100.0×10 13 / m 2 Therefore, the total elongation T.EL is less than 14.0%, and sufficient processability cannot be obtained.

[0530] In test numbers 36 and 37, the B content was too low. Therefore, in the microstructure of the hot-rolled steel sheet, the area ratio of bainitic ferrite was less than 85%. In addition, the average equivalent circle diameter of Ti carbides in the hot-rolled steel sheet exceeded 10 nm. In addition, the dislocation density was less than 8.0×10 13 / m 2 Therefore, the tensile strength TS is less than 780 MPa, and sufficient strength cannot be obtained. Furthermore, the yield ratio YR is less than 85%, and sufficient rigidity cannot be obtained. Furthermore, sufficient LME resistance cannot be obtained.

[0531] In test numbers 38 and 39, the B content was too high. Therefore, the dislocation density of the hot-rolled steel sheets exceeded 100.0×10 13 / m 2 Therefore, the total elongation T.EL is less than 14.0%, and sufficient processability cannot be obtained. Furthermore, sufficient LME resistance cannot be obtained.

[0532] In test numbers 40 and 41, the content of each element in the chemical composition of the hot-rolled steel sheet was appropriate. However, the finishing temperature FT in the manufacturing process was too high. Therefore, the average equivalent circle diameter of the grains of bainitic ferrite in the hot-rolled steel sheet exceeded 15 μm. As a result, the yield ratio YR was less than 85%, and sufficient rigidity could not be obtained.

[0533] In test numbers 42 and 43, the content of each element in the chemical composition of the hot-rolled steel sheet was appropriate. However, the cooling rate CR1 in the first stage of the cooling process of the manufacturing process was too fast. Therefore, polygonal ferrite was generated in the microstructure of the hot-rolled steel sheet, and the area ratio of bainitic ferrite was less than 85%. In addition, the dislocation density of the hot-rolled steel sheet was less than 8.0×10 13 / m 2 As a result, the yield ratio YR is less than 85%, and sufficient rigidity cannot be obtained.

[0534] In test numbers 44 and 45, the content of each element in the chemical composition of the hot-rolled steel sheet is appropriate. However, the switching temperature ST of the cooling process in the manufacturing process is too high. Therefore, the austenite grains become coarse, and the average equivalent circle diameter of the bainitic ferrite of the hot-rolled steel sheet exceeds 15 μm. As a result, the yield ratio YR is less than 85%, and sufficient rigidity cannot be obtained.

[0535] In test numbers 46 and 47, the content of each element in the chemical composition of the hot-rolled steel sheet was appropriate. However, the switching temperature ST of the cooling process in the manufacturing process was too low. Therefore, polygonal ferrite was generated in the microstructure of the hot-rolled steel sheet, and the area ratio of bainitic ferrite was less than 85%. In addition, the dislocation density of the hot-rolled steel sheet was less than 8.0×10 13 / m 2 As a result, the yield ratio YR is less than 85%, and sufficient rigidity cannot be obtained.

[0536] In test numbers 48 and 49, the content of each element in the chemical composition of the hot-rolled steel sheet was appropriate. However, the cooling rate CR2 in the latter stage of the cooling process of the manufacturing process was too slow. Therefore, polygonal ferrite was generated in the microstructure of the hot-rolled steel sheet, and the area ratio of bainitic ferrite was less than 85%. In addition, the dislocation density of the hot-rolled steel sheet was less than 8.0×10 13 / m 2 Moreover, the average equivalent circle diameter of Ti carbides exceeded 10 nm. Therefore, the tensile strength TS was less than 780 MPa, and sufficient strength could not be obtained. Moreover, the yield ratio YR was less than 85%, and sufficient rigidity could not be obtained.

[0537] In test numbers 50 and 51, the content of each element in the chemical composition of the hot-rolled steel sheet was appropriate. However, the coiling temperature CT in the coiling process was too high. Therefore, polygonal ferrite was generated in the microstructure of the hot-rolled steel sheet, and the area ratio of bainitic ferrite was less than 85%. In addition, the average equivalent circle diameter of Ti carbides exceeded 10 nm. In addition, the dislocation density of the hot-rolled steel sheet was less than 8.0×10 13 / m 2 Therefore, the tensile strength TS is less than 780 MPa, and sufficient strength cannot be obtained. Furthermore, the yield ratio YR is less than 85%, and sufficient rigidity cannot be obtained.

[0538] In test numbers 52 to 54, the content of each element in the chemical composition of the hot-rolled steel sheet was appropriate. However, the coiling temperature CT in the coiling process was too low. Therefore, bainite was generated in the microstructure of the hot-rolled steel sheet. As a result, the area ratio of bainitic ferrite was less than 85%, and the dislocation density of the hot-rolled steel sheet exceeded 100.0×10 13 / m 2 Therefore, the total elongation T.EL is less than 14.0%, and sufficient processability cannot be obtained.

[0539] The embodiments of the present disclosure have been described above. However, the above embodiments are merely examples for implementing the present disclosure. Therefore, the present disclosure is not limited to the above embodiments, and the above embodiments can be appropriately modified and implemented within the scope of the present disclosure.

Claims

1. A hot-rolled steel sheet, which comprises, by mass%, C: 0.040 to 0.120%, Si: 0.01-0.60%, Mn: 0.50-1.50%, P: 0.025% or less, S: 0.010% or less, Al:0.010~0.070%、 N: 0.0070% or less, Ti: 0.055~0.200%, B:0.0010~0.0050%、 Nb: 0-0.20%, V:0~0.20%、 Cr:0~1.0%、 Mo: 0 to 1.0%, and The balance is Fe and impurities. In the microstructure, the area ratio of bainitic ferrite is more than 90%. The dislocation density is 8.0×10 13 / m 2 ~100.0×10 13 / m 2 , The average circle-equivalent diameter of Ti carbides in the hot-rolled steel sheet is 10 nm or less. The average circle-equivalent diameter of the bainitic ferrite grains is 15 μm or less.

2. The hot rolled steel sheet according to claim 1, wherein: The steel sheet contains one or more selected from the group consisting of Nb: 0.01 to 0.20%, V: 0.01 to 0.20%, Cr: 0.1 to 1.0%, and Mo: 0.1 to 1.0%.

3. A hot-dip galvanized steel sheet comprising: The hot rolled steel sheet according to claim 1 or claim 2; and The hot-dip galvannealed coating layer is formed on the surface of the hot-rolled steel sheet and contains 65.00% or more of Zn in terms of mass%.

4. A method for producing a hot-rolled steel sheet, which is the method for producing a hot-rolled steel sheet according to claim 1 or claim 2, comprising: A rough rolling process uses a rough rolling mill to perform rough rolling on the billet to produce a rough bar; a finishing rolling step of performing finish rolling on the rough bar material using a finishing rolling mill to produce a steel plate, wherein the finishing rolling temperature FT is set to 850° C. to 950° C.; A cooling process, cooling the steel plate after finish rolling; and a coiling step of coiling the steel sheet after the cooling step at a coiling temperature of 470° C. to 620° C., In the cooling process, within 3 seconds after the finish rolling is completed, the cooling of the steel plate using a cooling device is started, When the period from the start of cooling by the cooling device until the temperature of the steel sheet reaches the switching temperature ST is defined as the front cooling period, and the period from the switching temperature ST until the temperature of the steel sheet reaches the coiling temperature is defined as the back cooling period, The front stage cooling rate CR1, which is the cooling rate in the front stage cooling period, is set to less than 25°C / sec. The switching temperature ST is set to 730°C to 830°C, The latter cooling rate CR2, which is the cooling rate in the latter cooling period, is set to 25° C. / sec or more.

Citation Information

Patent Citations

  • High strength hot rolled steel sheet and manufacturing method therefor

    JP2017179539A

  • High strength and high processability hot rolled steel sheet and manufacturing method therefor

    JP2018003062A

  • HIGH STRENGTH MOLTEN Zn-Al-Mg-BASED PLATED STEEL SHEET FOR AUTOMOBILE COMPONENT EXCELLENT IN FLEXURE PROCESSABILITY AND AUTOMOBILE COMPONENT USING THE SAME

    JP2018145500A

  • Hot-rolled steel sheet

    CN105102658A

  • High-strength hot-rolled steel sheet

    WO2021210644A1